Automated methods to accelerate fungal red listing: a case study for North American macrofungi - Vida J. Svahnström; Steven Bachman; Cátia Canteiro; Eimear Nic Lughadha; A. Martyn Ainsworth; Jessica L. Allen; Scott T. Bates; Matilda J.M. Brown; Susana P. Cunha; Anders Dahlberg; Susana C. Gonçalves; Tom W. May; et al. (Fungal Ecology, 2026)

Prenatal exposure to indoor PM2.5 and children's cognitive performance at 4 years of age: an observational analysis from the UGAAR randomized controlled trial - Battsetseg Ulziikhuu; Enkhjargal Gombojav; Chimeglkham Banzrai; Sarangerel Batsukh; Enkhtuul Enkhtuya; Buyantushig Boldbaatar; David C. Bellinger; Bruce P. Lanphear; Lawrence C. McCandless; Xing Yu; Ryan W. Allen (Environmental Pollution, 2026)

Hybrid dispersion and chemical transport modeling frameworks for characterizing sources of ambient hydrocarbons in the Permian Basin - Joel D. Graves; Zhichao Chen; Qining Chen; Yosuke Kimura; V'Jae Navarro Brown; David T. Allen (Atmospheric Environment, 2026)

Can environmental, social, and governance rating divergence harm the green total factor productivity? Evidence from Chinese listed firms - Junlin He; Kok-Haur Ng; Wee-Yeap Lau; David Allen; Wei-Theng Lau (Journal of Environmental Management, 2026)

Adaptation and Response in Drylands: A Dryland Research Agenda and Campaign Strategy - Andrew F. Feldman; Sasha C. Reed; Konrad Wessels; Dennis Ojima; David J. P. Moore; William K. Smith; Niall P. Hanan; Cibele Amaral; Flurin Babst; Joel A. Biederman; Marcy Litvak; Natasha MacBean; et al. (Global Change Biology, 2026)
Dryland ecosystems cover 41% of Earth's land surfaces, account for 44% of cultivated lands and 60% of food sources, and make large contributions to the global water and carbon cycles. However, these ecosystems are experiencing unprecedented extremes including heatwaves, floods, and droughts as well as hotter temperatures and often declining water resource availability. These ecosystems are some of the most challenging to monitor given their high temporal variability with rapid response to their environment as well as vast spatial variability with intermixing of different plant species and life forms amongst bare soil coverage. The Adaptation and Response in Drylands (ARID) campaign was selected by National Aeronautics and Space Administration (NASA) as a scoping study to develop a research agenda for a dryland field campaign. Here, we detail our ARID science research agenda and implementation plan that were developed based on an extensive community engagement effort in over 160 events with over a thousand scientists, land managers, and Tribal communities between 2023 and 2024. The selected science themes cover drought and climate variability, ecosystem structure, function, and biodiversity, carbon cycle interannual variability and trends, and social ecological systems (land management and adaptation). We then detail our remote sensing, modeling, and field‐based strategies to capture high temporal and high spatial resolution processes. Finally, our implementation strategy is presented which includes focus area selections in a core intensive western U.S. domain and distributed international domains. This strategy includes our overarching guiding principles of using multi‐temporal airborne acquisitions and super sites as well as enhancing land management in co‐development with end‐user partners. While originally developed for NASA, our ARID report creates a blueprint for any future dryland field campaign, at any scale, that can be implemented widely for foundational and applied science objectives.

Toward an integrated understanding of animal weapons - Christine W. Miller; Dominic Cram; Sarah M. Lane; Romain Boisseau; Sophia Fitzgerald; Nicole Lopez; Allen J. Moore; Christina J. Painting; Alexandre V. Palaoro; Michael Ryan; Ummat Somjee; Camille Thomas-Bulle; et al. (Trends in Ecology & Evolution, 2026)

In situ evaluation of an active-passive sampling (APS) technique for monitoring psychoactive compounds in effluent wastewater - Allen Jun Anies; Maria Laimou-Geraniou; Maarten Quireyns; Tim Boogaerts; Cara Byns; Taja Verovšek; David Heath; Ester Heath; Alexander L.N. van Nuijs; Adrian Covaci; Ronny Blust; Raewyn M. Town (Environmental Pollution, 2026)

A climate region classification for California’s warm season: apparent temperature clustering to support heat-health epidemiology - Marinelle Villanueva; Sydney Monte-Sano; Scott Sheridan; Michael Allen; Laurence Kalkstein; Michael Jerrett; David P. Eisenman (International Journal of Biometeorology, 2026)
Climate classification enhances our understanding of regional climate patterns and enables a science-based framework for assessing environmental and public health relationships. Prior climate classification systems are limited in their ability to capture variation across dynamic subclimates, particularly in the context of complex topographical, elevation, and meteorological characteristics such as California, United States. In this study, we spatially classified climate regions in California during the warm season (May through September) in 2021 and 2022. We applied principal component analysis with k-means clustering algorithms to gridded data consisting of apparent temperature during the study period as a monthly time series. We then performed statistical and spatial analysis to delineate the geographical extent of climate regions with shared apparent temperature distributions. The results of this study include a statewide map of 30 warm season climate regions based on meteorological data characterized by homogenous temperature patterns that are distinct from one another. The climate regions demonstrate highly variable spatial patterns of heat exposures and often span across and within multiple county boundaries. The methods we present within a complex geography can be readily adapted to other regional settings and updated to other temporal periods. This study informs our understanding of regional climate patterns during the warm season and is applicable to the development of early warning systems and quantifying extreme heat impacts across statewide populations.

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Quadriceps mitochondrial DNA quantity, quality, and gene expression after 2 years of calorie restriction: exploratory results from the CALERIE trial - Jayanta K. Das; Yu Zhang; Leanne M. Redman; Corby K. Martin; Sai Krupa Das; Susan B. Racette; Allen Herbst; Nianjun Liu; David B. Allison; Debbie McKenzie; Judd M. Aiken; Steve Horvath; et al. (GeroScience, 2026)
The Comprehensive Assessment of Long-term Effects of Reducing Intake of Energy (CALERIE)™ trial was a randomized, 2-year controlled trial of caloric restriction (CR) versus an ad libitum (AL) control condition in nonobese humans. We performed exploratory analyses of muscle mitochondrial DNA (mtDNA) integrity, one element of mitochondrial quality. Our aims were to assess the feasibility of this approach, explore associations to inform future hypotheses, estimate effect sizes and statistical power for subsequent studies, and contribute additional data to the CALERIE database. We used droplet digital PCR to quantitate the copy numbers of nuclear DNA, mtDNA, and mtDNA deletion mutations in remnant total DNA samples extracted from quadriceps biopsies at baseline ( n = 93), 12 months ( n = 44), and 24 months ( n = 31). MtDNA copy number and mutation frequency were correlated with existing gene expression data from the same muscle biopsies. MtDNA copy number was lower in females ( p = 0.0005) and declined over time ( p = 0.0001), with no statistically significant differences observed for CR versus AL ( p = 0.2898) or age across both groups ( p = 0.4644). Baseline copy number correlated positively with baseline physiological measures including fat-free mass ( r = 0.43, p = 2e−05), self-reported energy intake ( r = 0.34, p = 0.00077), resting metabolic rate ( r = 0.42, p = 0.00261), total energy expenditure ( r = 0.31, p = 0.00261), and V̇O₂max ( r = 0.41, p = 1e−04), and with gene expression related to mitochondrial function, while showing negative correlations with nuclear genome maintenance, RNA splicing, and ribosomes. MtDNA mutation frequency increased with age ( p = 0.0041) and showed a weak negative correlation with V̇O 2 max ( r = −0.23, p = 3e−05). MtDNA mutation frequency was not statistically different with CR. Mutation frequency was positively correlated with gene expression changes in inflammation and negatively correlated with protein translation. We observed that, as expected, mtDNA copy number declined over time, was lower in females, and correlated with metabolic measures and mitochondrial gene expression, suggesting its potential utility as a marker of metabolic health. These findings contribute to understanding mitochondrial adaptations to CR and highlight potential benefits of CR interventions. Graphical Abstract

Correction to: Evaluation of acid rain in urban areas of the United States of America and Mexico from 2003 to 2019 - Amelia Jiménez Alcántara; Rodolfo Sosa Echeverría; David Allen Gay; Ana Luisa Alarcón Jiménez (Environmental Monitoring and Assessment, 2026)

Restoring a Healthier Nerve Phenotype: Mechanistic Insights into High-Concentration Capsaicin Topical System (HCCTS) for Painful Diabetic Peripheral Neuropathy (PDPN) - David M. Simpson; Samuel Allen; Audrey Carnevale; Jennifer Lohf (Toxicon, 2026)

Comparing the Impact of the High-Concentration Capsaicin Topical System (HCCTS) on Pain and Sleep in Patients With Painful Diabetic Peripheral Neuropathy (PDPN): Findings from the STEP Randomized Trial and the Real-World CASPAR Study - David M. Simpson; Samuel Allen; Audrey Carnevale; Lizandra Marcondes; Mariëlle Eerdekens (Toxicon, 2026)

Evaluation of acid rain in urban areas of the United States of America and Mexico from 2003 to 2019 - Amelia Jiménez Alcántara; Rodolfo Sosa Echeverría; David Allen Gay; Ana Luisa Alarcón Jiménez (Environmental Monitoring and Assessment, 2026)

Implications for modeling anion exchange treatment of perfluoroalkyl substances in drinking water and related natural organic impacts: a pilot study - Samantha J. Smith; David G. Wahman; Eric J. Kleiner; Brooke N. Gray; Toby T. Sanan; Eva K. Stebel; Cameron X. Gastaldo; Esther W. Hughes; Sophia G. Pedigo; Boris Datsov; Malcolm F. Lathrop-Allen; Isabella L. Bass; et al. (Water Research, 2026)

deadtrees.earth — An open-access and interactive database for centimeter-scale aerial imagery to uncover global tree mortality dynamics - Clemens Mosig; Janusch Vajna-Jehle; Miguel D. Mahecha; Yan Cheng; Henrik Hartmann; David Montero; Samuli Junttila; Stéphanie Horion; Mirela Beloiu Schwenke; Michael J. Koontz; Khairul Nizam Abdul Maulud; Stephen Adu-Bredu; et al. (Remote Sensing of Environment, 2026)

Foraminiferal and environmental change across the younger Dryas chronozone, NW Baffin Bay - Stephen J. Culver; David J. Mallinson; Seth R. Sutton; Christopher R. Moore; Allen West; Malcolm A. LeCompte (Quaternary Science Reviews, 2025)

Corrigendum to “Subchronic inhalation exposure to ultrafine particulate matter alters the intestinal microbiome in various mouse models” [Environ. Res. 248 (2024) 118242] - Candace Chang; Rajat Gupta; Farzaneh Sedighian; Allen Louie; David M. Gonzalez; Collin Le; Jae Min Cho; Seul-Ki Park; Jocelyn Castellanos; To-Wei Ting; Tien S. Dong; Nerea Arias-Jayo; et al. (Environmental Research, 2025)

Transportation in net-zero emissions futures: Insights from the EMF-37 model intercomparison study - Christopher Hoehne; Matteo Muratori; John Bistline; Carol Lenox; David L. McCollum; Morgan Browning; Kara Podkaminer; Robert H. Beach; Robbie Orvis; Shiqi Ou; Page Kyle; Sharyn Lie; et al. (Energy and Climate Change, 2025)

Overview of BLOOFINZ/INDITUN investigations of the southern bluefin spawning region off northwest Australia, January–March 2022 - Michael R. Landry; Raúl Laiz-Carrión; Sven A. Kranz; Karen E. Selph; Michael R. Stukel; Estrella Malca; David Die; Lynnath E. Beckley; Moira Décima; Rasmus Swalethorp; José M. Quintanilla; Natalia Yingling; et al. (Deep Sea Research Part II: Topical Studies in Oceanography, 2025)

IND-enabling preclinical studies of [11C]COU, a trapped metabolite PET radiotracer for monoamine oxidase-B - Madison S. Frazier; Tanpreet Kaur; Jenelle Stauff; Wade P. Winton; Bradford D. Henderson; Alexandra S. Dumond; Xia Shao; David M. Raffel; Kirk A. Frey; Michael R. Kilbourn; Allen F. Brooks; Peter J. H. Scott (Medicinal Chemistry Research, 2025)
[ 11 C]COU is a trapped metabolite radiotracer for in vivo analysis of Monoamine Oxidase B activity using positron emission tomography (PET) imaging. [ 11 C]COU has the potential to quantify astrocytosis in the early stages of Alzheimer’s disease, providing an earlier marker of disease than currently available for staging disease progression. Prior preclinical studies have demonstrated the efficacy of this radiotracer in preclinical imaging studies, warranting the translation for clinical evaluation. In this paper, we describe results of the requisite preclinical studies required to obtain approval for translation of [ 11 C]COU into first-in-human studies. Development and validation of a production method that conforms to the quality requirements described in the US Pharmacopeia was accomplished, along with preclinical rodent studies to determine human radiation dose estimates and a single acute dose pharmacology and toxicology study to establish that an injected mass dose 100-fold higher than the proposed PET imaging dose was below the no-observed-adverse-effect level (NOAEL). The production method was validated in triplicate, yielding [ 11 C]COU in sufficient radiochemical yield (9.3 ± 0.008%), radiochemical purity (99.2 ± 0.002%) and molar activity (165 ± 65 TBq/mmol) for routine clinical use, and providing a product that was sterile and met (or exceeded) all quality control requirements for human use. Dosimetric analysis determined that the effective human dose of [ 11 C]COU is 0.005 mSv/MBq, also acceptable for clinical use. Lastly, no observable adverse effects were noted at 86 μg/kg in rodent toxicology studies (100x the proposed human dose). From these results we received approval to advance [ 11 C]COU into clinical studies.

Species Richness Gradients Vary Across Phylogenetic Scales - Antonin Machac; Allen Hurlbert; Juliano Sarmento Cabral; Felipe O. Cerezer; Cristian S. Dambros; Susanne Fritz; Catherine H. Graham; Oskar Hagen; Florian Hartig; Shan Huang; Mikael Pontarp; David Storch (Global Ecology and Biogeography, 2025)
Aim To determine how species richness gradients—commonly considered universal—vary across the phylogenetic hierarchy of birds and mammals, and to uncover how clade age and size predetermine the gradients. Location Global. Time Period Last 120 million years. Taxa Studied Birds and mammals (~15,000 species). Methods We used large‐scale phylogenies of birds and mammals and captured the species richness gradient for each of their monophyletic clades. Gradient strength was quantified with respect to latitude, environmental productivity and temperature using multiple measures (raw slopes, log transformation, log–log transformation, and correlations). To distinguish statistical from biological effects, we compared the observed gradients to those generated by null models that randomly reassigned species to clades while preserving the phylogeny and species distributions. Results Species richness gradients show considerable variation. Small and young clades exhibited inconsistent gradients—including reverse or flat gradients—while older and larger clades converged on steep, consistent gradients. Even moderately large clades (~500 species) commonly displayed reverse gradients. Null models replicated this trend but only partially, implying that biological effects also drive gradient variation. These phylogenetic trends were sensitive to the choice of gradient measure: raw slopes frequently inflated the strength of this trend and the apparent differences among clades, while log and log–log transformations revealed only moderate trends. Main Conclusions Species richness gradients are not universal, nor are they phylogenetic scale‐invariant. Instead, they follow systematic trends across the phylogenetic hierarchy. Young, small clades often bear signatures of their region of origin and historical dispersal, whereas older, larger clades converge on similar gradients. Recognising the variation and the phylogenetic trends within it elucidates the formation of biodiversity patterns. We offer guidelines for choosing gradient measures, arguing that multiple metrics, combined with careful use of null models, are necessary for a nuanced understanding of how, and why, global biodiversity patterns diverge from the presumed universal gradients.

Motivations and barriers to integrated management of annual bluegrass in sports fields: US survey findings - David E. Ervin; George B. Frisvold; Jennifer H. Allen; Aaron J. Patton; James T. Brosnan; Rebecca Grubbs Bowling; Mathew T. Elmore; Muthukumar V. Bagavathiannan; James D. McCurdy; Travis W. Gannon; John E. Kaminski; Alec R. Kowaleski; et al. (Urban Forestry & Urban Greening, 2025)

Taking Health into Your Own Hands: Evaluating Patient and Provider Perspectives of Human Papillomavirus Self-Sampling for Cervical Cancer Screenings and Opportunities for Education - Stella Roth; Breanne Lott; Jerlin Garo; Jordan Allen; Sara Krivacsy; Emily Buttigieg; Jessica Atrio; Maria Young; David Cepeda; Brittany Miller; Amr Soliman (Journal of Cancer Education, 2025)

Ocular Motor and Vestibular Profile in Spinocerebellar Ataxia Type 27B: Toward a Practical Bedside Diagnostic Framework - Leonardo Eleuterio Ariello; Daniel R. Gold; Weiyi Mu; Michael C. Schubert; Claire Allen; Ashley Paul; David P.W. Rastall (The Cerebellum, 2025)

Combining analysis of individual and wastewater whole genome sequencing improves SARS-CoV-2 surveillance - Evan P. Troendle; Andrew J. Lee; Marina I. Reyne; Danielle M. Allen; Stephen J. Bridgett; Clara H. Radulescu; Michael Glenn; John-Paul Wilkins; Francesco Rubino; Behnam Firoozi Nejad; Cormac McSparron; Marc Niebel; et al. (Water Research, 2025)

What is ‘good evidence’ for environmental decision making? Insights from professionals working at the science-policy interface - Elizabeth A. Nyboer; Andrew N. Kadykalo; Nathan Young; Vivian M. Nguyen; Trina Rytwinski; John-Francis Lane; Joseph R. Bennett; Nathan Harron; Susan M. Aitken; Graeme Auld; David Browne; Aerin L. Jacob; et al. (Environmental Science & Policy, 2025)

Actor-network analysis of partners facilitating regenerative ranching practices in the US Northern Great Plains - Timothy Pape; Gwendŵr Meredith; David Sandahl; Md Faizul Kabir; Simanti Banerjee; Craig Allen; Elliott Dennis; Mitchell Stephenson (Rangelands, 2025)

The influence of mycorrhizal hyphal connections and neighbouring plants on Plantago lanceolata physiology and nutrient uptake - Henry W. G. Birt; Lewis P. Allen; Sam Madge; Clare H. Robinson; Richard D. Bardgett; David Johnson (Mycorrhiza, 2025)
Most plants extend their zone of interaction with surrounding soils and plants via mycorrhizal hyphae, which in some cases can form common mycorrhizal networks with hyphal continuity to other neighbouring plants. These interactions can impact plant health and ecosystem function, yet the role of these radial plants in mycorrhizal interactions and subsequent plant performance remains underexplored. Here we investigated the influence of hyphal exploration and interaction with neighbouring mycorrhizal plants, plants that are weakly mycorrhizal, and a lack of neighbouring plants on the performance of Plantago lanceolata , a mycotrophic perennial herb common to many European grasslands, using mesh cores and the manipulation of neighbouring plant communities. Allowing growth of hyphae beyond the mesh core increased carbon capture above-ground and release below-ground as root exudates and resulted in the greater accumulation of elements relevant to plant health in P. lanceolata . However, contrary to expectations, the presence of mycorrhizal, or weakly mycorrhizal neighbours as well as an absence of neighbours did not significantly alter the benefits of hyphal networks to P. lanceolata . Our findings demonstrate that enabling the development of a fungal network beyond the immediate host rhizosphere significantly influences plant leaf elemental stoichiometry, enhances plant carbon capture, and increases the amount of carbon they release via their roots as exudates. Our experimental design also provides a simple set of controls to prevent attributing positive mycorrhizal effects to neighbouring plant connections.

Optimizing automated photo identification for population assessments - Philip T. Patton; Krishna Pacifici; Robin W. Baird; Erin M. Oleson; Jason B. Allen; Erin Ashe; Aline Athayde; Charla J. Basran; Elsa Cabrera; John Calambokidis; Júlio Cardoso; Emma L. Carroll; et al. (Conservation Biology, 2025)
Several legal acts mandate that management agencies regularly assess biological populations. For species with distinct markings, these assessments can be conducted noninvasively via capture‐recapture and photographic identification (photo‐ID), which involves processing considerable quantities of photographic data. To ease this burden, agencies increasingly rely on automated identification (ID) algorithms. Identification algorithms present agencies with an opportunity—reducing the cost of population assessments—and a challenge—propagating misidentifications into abundance estimates at a large scale. We explored several strategies for generating capture histories with an ID algorithm, evaluating trade‐offs between labor costs and estimation error in a hypothetical population assessment. To that end, we conducted a simulation study informed by 39 photo‐ID datasets representing 24 cetacean species. We fed the results into a custom optimization tool to discern the optimal strategy for each dataset. Our strategies included choosing between truly and partially automated photo‐ID and, in the case of the latter, choosing the number of suggested matches to inspect. True automation was optimal for datasets for which the algorithm identified individuals well. As identification performance declined, the optimization recommended that users inspect more suggested matches from the ID algorithm, particularly for small datasets. False negatives (i.e., individual was resighted but erroneously marked as a first capture) strongly predicted estimation error. A 2% increase in the false negative rate translated to a 5% increase in the relative bias in abundance estimates. Our framework can be used to estimate expected error of the abundance estimate, project labor effort, and find the optimal strategy for a dataset and algorithm. We recommend estimating a strategy's false negative rate before implementing the strategy in a population assessment. Our framework provides organizations with insights into the conservation benefits and consequences of automation as conservation enters a new era of artificial intelligence for population assessments.

Scaling up eco-engineering: The role of topographic complexity and spatial variability in shaping biodiversity on coastal structures - Charlotte H. Clubley; Antony M. Knights; Jessica Allen; David T. Bilton; Andy Foggo; Mick E. Hanley; James Murphy; Louisa E. Wood; Louise B. Firth (Science of The Total Environment, 2025)

Reconciling scale using the Resist-Accept-Direct (RAD) Framework to improve management of woody encroachment in grasslands - Rheinhardt Scholtz; Daniel R. Uden; Brady W. Allred; Victoria M. Donovan; Jeremy D. Maestas; Scott L. Morford; Matthew O. Jones; David E. Naugle; Samantha M. Cady; Dillon T. Fogarty; Alexander L. Metcalf; Brian Chaffin; et al. (Journal of Environmental Management, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

Carbon stock, subsurface characteristics and accommodation settings of sub-tropical peatland Histosols, K'gari, Queensland Australia - Gareth Chalmers; Zeinab Ghasemzadeh; David Chittleborough; Allen Gontz; Iroshaka Gregory Cooray; Catherine Yule; Darshanaa Chellaiah; Adrian McCallum (Geoderma Regional, 2025)

Exposed and Vulnerable: Sources and Health Implications of Chemical Exposures in Neonatal, Pediatric, and Cardiac Intensive Care Units - Jordan R. Kuiper; Melania Bembea; J. William Gaynor; David Graham; Eric M. Graham; Kurunthachalam Kannan; Nikki G. Posnack; Allen D. Everett; Jessie P. Buckley (Current Environmental Health Reports, 2025)

Efficacy, non-target impacts, and costs of mechanical control options against a bioturbator in bivalve aquaculture - Jennifer L. Ruesink; C. Haleh Mawson; Brian Allen; Jeffrey Barrett; David Beugli; Steven Booth; Laura Butler; Bill Dewey; Cinde R. Donoghue; Brett R. Dumbauld; Kristine Feldman; Zachary Forster; et al. (Aquaculture, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Site‐Specific Nutrient Data Reveal the Importance of Soils in Driving the Mycorrhizal Make‐Up of Woody Vegetation Worldwide - Xiaobin Hua; Christopher H. Lusk; Ian A. Dickie; Stephen Adu‐Bredu; Kathryn J. Allen; Viviana Araus; Laurent Augusto; Pavel Barsukov; David Bauman; Félix Brédoire; David F. R. P. Burslem; James W. Dalling; et al. (Global Ecology and Biogeography, 2025)
Aim Arbuscular mycorrhizas (AM) and ectomycorrhizas (ECM) have different impacts on nutrient cycling, carbon storage, community dynamics and enhancement of photosynthesis by rising CO 2 . Recent global analyses have concluded that patterns of AM/ECM dominance in forests worldwide are shaped by climate, with soil nutrients contributing negligible additional explanatory power. However, their reliance on nutrient data from GIS surfaces masks important local influences of parent material, topography and soil age on soil nutrient status. We asked if use of site‐specific nutrient data reveals a more important role for nutrients. Time Period Present day. Location Global dataset comprising 703 sites, encompassing forests, savanna/woodlands, shrublands and deserts on all continents except Antarctica. Taxa Studied Arborescent plants, including angiosperms, gymnosperms and tree ferns. Methods Generalised Additive Models for Location, Scale and Shape (GAMLSS) to determine the effects of climate variables, soil nitrogen and soil phosphorus on the proportional representation of ECM and of non‐mycorrhizal species (NM) in woody vegetation. Results GAMLSS showed a strong negative relationship of ECM representation with mean annual temperature (MAT), and a strong negative relationship with soil total nitrogen. NM representation was highest on dry sites and phosphorus‐poor sites. Reanalysis showed that GIS‐derived soil nutrient data had less explanatory power than site‐specific nutrient data, and resulted in poorer model fits. Conclusions Our results support the long‐held belief that soil nutrients as well as climate influence the relative fitness of different mycorrhizal syndromes worldwide, and demonstrate the value of using site‐specific nutrient data. Soil nutrients should be considered when predicting the impact of climate change on the mycorrhizal composition of vegetation and resulting shifts in ecosystem processes.

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Natural shading is helpful but not sufficient for mitigating warming in green sea turtle nests in the tropical South China Sea - Tsung-Han Liu; Ming-Shiou Jeng; Chan-Yuan David Lee; Chih-Wei Tu; Po-Hsiung Lin; Chaolun Allen Chen; Chia-Ying Ko (Biological Conservation, 2024)

The long-chain polyfluorinated alkyl substance perfluorohexane sulfonate (PFHxS) promotes bone marrow adipogenesis - Laimar C. Garmo; Mackenzie K. Herroon; Shane Mecca; Alexis Wilson; David R. Allen; Manisha Agarwal; Seongho Kim; Michael C. Petriello; Izabela Podgorski (Toxicology and Applied Pharmacology, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Lactococcus lactis MA5 is a potential autochthonous probiotic for nutrient digestibility enhancement and bacterial pathogen inhibition in hybrid catfish ( Ictalurus punctatus × I. furcatus ) - Jing Huang; Heather R. Jordan; Caitlin E. Older; Matt J. Griffin; Peter J. Allen; David J. Wise; Penelope M. Goodman; J. Grant Reifers; Fernando Y. Yamamoto (Journal of Fish Diseases, 2024)
With the emergence of diseases, the U.S. catfish industry is under challenge. Current trends prefer autochthonous bacteria as potential probiotic candidates owing to their adaptability and capacity to effectively colonize the host's intestine, which can enhance production performance and bolster disease resistance. The objective of this study was to isolate an autochthonous bacterium as probiotic for hybrid catfish. Initially, an analysis of the intestinal microbiota of hybrid catfish reared in earthen ponds was conducted for subsequent probiotic development. Twenty lactic acid bacteria were isolated from the digesta of overperforming catfish, and most of the candidates demonstrated probiotic traits, including proteolytic and lipolytic abilities; antagonistic inhibition of catfish enteric bacterial pathogens, negative haemolytic activity and antibiotic susceptibility. Subsequent to this screening process, an isolate of Lactococcus lactis (MA5) was deemed the most promising probiotic candidate. In silico analyses were conducted, and several potential probiotic functions were predicted, including essential amino acids and vitamin synthesis. Moreover, genes for three bacteriocins, lactococcin A, enterolysin A and sactipeptide BmbF, were identified. Lastly, various protectant media for lyophilization of MA5 were assessed. These findings suggest that Lactococcus lactis MA5 can be an autochthonous probiotic from hybrid catfish, holding promise to be further tested in feeding trials.

LiveWellNow: Soldier Feedback on an Innovative Interactive Digital Food Environment System in a Military Food Environment - Jared McGuirt; Kathryn Polaskey; Robert E. Anderson; David Gaviria; Julianna Jayne; Holly McClung; Alison Gustafson; Kendall Allen; Anastassia Skarlinski; Cheyenne Thaxton; Teresa Pearce; Alice Ammerman (Journal of Nutrition Education and Behavior, 2024)

Differences in the anatomy and physiology of the human and rat respiratory tracts and impact on toxicological assessments - Andreas O. Stucki; Ursula G. Sauer; David G. Allen; Nicole C. Kleinstreuer; Monique M. Perron; Krystle L. Yozzo; Anna B. Lowit; Amy J. Clippinger (Regulatory Toxicology and Pharmacology, 2024)

Towards a new impact geochronometer: Deformation microstructures and U-Pb systematics of shocked xenotime - Cilva Joseph; Denis Fougerouse; Aaron J. Cavosie; Hugo K.H. Olierook; Steven M. Reddy; Tommaso Tacchetto; Raiza R. Quintero; Allen Kennedy; David W. Saxey; William D.A. Rickard (Geochimica et Cosmochimica Acta, 2024)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Evaluation of in silico model predictions for mammalian acute oral toxicity and regulatory application in pesticide hazard and risk assessment - Patricia L. Bishop; Kamel Mansouri; William P. Eckel; Michael B. Lowit; David Allen; Amy Blankinship; Anna B. Lowit; D. Ethan Harwood; Tamara Johnson; Nicole C. Kleinstreuer (Regulatory Toxicology and Pharmacology, 2024)

Subchronic inhalation exposure to ultrafine particulate matter alters the intestinal microbiome in various mouse models - Candace Chang; Rajat Gupta; Farzaneh Sedighian; Allen Louie; David M. Gonzalez; Collin Le; Jae Min Cho; Seul-Ki Park; Jocelyn Castellanos; To-Wei Ting; Tien S. Dong; Nerea Arias-Jayo; et al. (Environmental Research, 2024)

Quantifying the impact of urban road traffic on air quality: activity pre-pandemic and during partial and full lockdowns - Nawaf S. Alhajeri; Fahad M. Al-Fadhli; Ahmed Aly; David T. Allen (Environmental Monitoring and Assessment, 2024)

Evidence of sociality and group foraging in Antarctic minke whales (Balaenoptera bonaerensis) - Jenny A. Allen; David E. Cade; Caroline B. Casey; Sarah Weindorf; David W. Johnston; Jacob M.J. Linsky; Jeremy A. Goldbogen; Doug P. Nowacek; Ari S. Friedlaender (Behavioral Ecology and Sociobiology, 2024)

Use of human predictive patch test (HPPT) data for the classification of skin sensitization hazard and potency - Matthias Herzler; Jaleh Abedini; David G. Allen; Dori Germolec; John Gordon; Hon-Sum Ko; Joanna Matheson; Emily Reinke; Judy Strickland; Hermann-Josef Thierse; Kim To; James Truax; et al. (Archives of Toxicology, 2024)
Since the 1940s, patch tests in healthy volunteers (Human Predictive Patch Tests, HPPTs) have been used to identify chemicals that cause skin sensitization in humans. Recently, we reported the results of a major curation effort to support the development of OECD Guideline 497 on Defined Approaches (DAs) for skin sensitization (OECD in Guideline No. 497: Defined Approaches on Skin Sensitisation, 2021a. https://doi.org/10.1787/b92879a4-en ). In the course of this work, we compiled and published a database of 2277 HPPT results for 1366 unique test substances (Strickland et al. in Arch Toxicol 97:2825–2837, 2023. https://doi.org/10.1007/s00204-023-03530-3 ). Here we report a detailed analysis of the value of HPPT data for classification of chemicals as skin sensitizers under the United Nations’ Globally Harmonized System of Classification and Labelling of Chemicals (GHS). As a result, we propose the dose per skin area (DSA) used for classification by the GHS to be replaced by or complemented with a dose descriptor that may better reflect sensitization incidence [e.g., the DSA causing induction of sensitization in one individual (DSA1+) or the DSA leading to an incidence of induction in 5% of the tested individuals (DSA05)]. We also propose standardized concepts and workflows for assessing individual HPPT results, for integrating multiple HPPT results and for using them in concert with Local Lymph Node Assay (LLNA) data in a weight of evidence (WoE) assessment. Overall, our findings show that HPPT results are often not sufficient for deriving unambiguous classifications on their own. However, where they are, the resulting classifications are reliable and reproducible and can be integrated well with those from other skin sensitization data, such as the LLNA.

Phytoplankton composition from sPACE: Requirements, opportunities, and challenges - Ivona Cetinić; Cecile S. Rousseaux; Ian T. Carroll; Alison P. Chase; Sasha J. Kramer; P. Jeremy Werdell; David A. Siegel; Heidi M. Dierssen; Dylan Catlett; Aimee Neeley; Inia M. Soto Ramos; Jennifer L. Wolny; et al. (Remote Sensing of Environment, 2024)

Forest soil classification for intensive pine plantation management: “Site Productivity Optimization for Trees” system - Rachel Cook; Thomas R. Fox; Howard Lee Allen; Chris W. Cohrs; Vicent Ribas-Costa; Andrew Trlica; Matthew Ricker; David R. Carter; Rafael Rubilar; Otávio Campoe; Timothy J. Albaugh; Pete Kleto; et al. (Forest Ecology and Management, 2024)

Retrospective evaluation of the eye irritation potential of agrochemical formulations - Neepa Choksi; Andreia Latorre; Shadia Catalano; Arthur Grivel; James Baldassari; Janaina Pires; Marco Corvaro; Mariana Silva; Maryanne Ogasawara; Monique Inforzato; Priscila Habe; Rosana Murata; et al. (Regulatory Toxicology and Pharmacology, 2024)

Geography, taxonomy, extinction risk and exposure of fully migratory birds to droughts and cyclones - Rhys G. G. Preston‐Allen; Henry Häkkinen; Laura Cañellas‐Dols; Eric I. Ameca y Juarez; C. David L. Orme; Nathalie Pettorelli (Global Ecology and Biogeography, 2024)
Aim Anthropogenic climate change is predicted to drive unprecedented increases in the frequency and intensity of extreme climatic events, such as drought and cyclones. The impacts of these events on fully migratory species could be particularly severe and have cascading effects on the functioning of many ecosystems. We explore the relationships between geography, taxonomy, extinction risk and the exposure of fully migratory birds to drought and cyclones. Location Global. Time Period 1985–2014. Major Taxa Studied 383 fully migratory bird species. Methods We assessed the exposure of fully migratory birds to cyclones and droughts, quantifying exposure by calculating the percentage of spatial overlap between a species' range and the extent of an extreme event within a given time series. We compared the level of cumulative exposure sustained by species among different taxonomic groups and within their breeding and wintering ranges; we also assessed whether species currently classed as ‘threatened’ are more cumulatively exposed than ‘non‐threatened’ species. Results We identified fully migratory bird species highly exposed to extreme climatic events and global geographic hotspots of species exposure. 4% of species were found to be highly exposed to cyclones and droughts in both their wintering and breeding ranges. Wintering ranges were, on average, more cumulatively exposed to cyclones than breeding ranges; there was no discernible difference in drought exposure between ranges. Species currently classed as threatened were shown to experience higher exposure to droughts than non‐threatened ones in both ranges. Main Conclusions This exposure analysis provides the first step to a full global assessment of fully migratory bird species' vulnerability to extreme climatic events. Many species are at least as exposed to extreme events within their wintering ranges as in their breeding ranges, supporting calls for ‘full cycle’ assessment of migratory species' vulnerability to climate change. Our identification of hotspots of exposure may help to guide further monitoring, research and management.

Preparation, analysis and toxicity characterisation of the redox metabolites of the azo food dye tartrazine - Ruth Pay; Abigail V. Sharrock; Riley Elder; Alaigne Maré; Joe Bracegirdle; Dan Torres; Niall Malone; Jan Vorster; Libusha Kelly; Ali Ryan; P. David Josephy; Emma Allen-Vercoe; et al. (Food and Chemical Toxicology, 2023)

Hydrodynamic response to bathymetric changes in Tampa Bay, Florida - Jing Chen; Yonggang Liu; Robert H. Weisberg; Steven A. Murawski; Sherryl Gilbert; David F. Naar; Lianyuan Zheng; Matthew Hommeyer; Catherine Dietrick; Mark E. Luther; Cheryl Hapke; Edward Myers; et al. (Deep Sea Research Part II: Topical Studies in Oceanography, 2023)

Practical Guide to Measuring Wetland Carbon Pools and Fluxes - Sheel Bansal; Irena F. Creed; Brian A. Tangen; Scott D. Bridgham; Ankur R. Desai; Ken W. Krauss; Scott C. Neubauer; Gregory B. Noe; Donald O. Rosenberry; Carl Trettin; Kimberly P. Wickland; Scott T. Allen; et al. (Wetlands, 2023)
Wetlands cover a small portion of the world, but have disproportionate influence on global carbon (C) sequestration, carbon dioxide and methane emissions, and aquatic C fluxes. However, the underlying biogeochemical processes that affect wetland C pools and fluxes are complex and dynamic, making measurements of wetland C challenging. Over decades of research, many observational, experimental, and analytical approaches have been developed to understand and quantify pools and fluxes of wetland C. Sampling approaches range in their representation of wetland C from short to long timeframes and local to landscape spatial scales. This review summarizes common and cutting-edge methodological approaches for quantifying wetland C pools and fluxes. We first define each of the major C pools and fluxes and provide rationale for their importance to wetland C dynamics. For each approach, we clarify what component of wetland C is measured and its spatial and temporal representativeness and constraints. We describe practical considerations for each approach, such as where and when an approach is typically used, who can conduct the measurements (expertise, training requirements), and how approaches are conducted, including considerations on equipment complexity and costs. Finally, we review key covariates and ancillary measurements that enhance the interpretation of findings and facilitate model development. The protocols that we describe to measure soil, water, vegetation, and gases are also relevant for related disciplines such as ecology. Improved quality and consistency of data collection and reporting across studies will help reduce global uncertainties and develop management strategies to use wetlands as nature-based climate solutions.

The influence of wildfire on invasive plant abundance and spatial structure in eastern ponderosa pine savanna - Victoria M. Donovan; Carissa L. Wonkka; Caleb P. Roberts; David A. Wedin; Devan Allen McGranahan; Dirac Twidwell (Plant Ecology, 2023)

A database of human predictive patch test data for skin sensitization - Judy Strickland; Jaleh Abedini; David G. Allen; John Gordon; Victoria Hull; Nicole C. Kleinstreuer; Hon-Sum Ko; Joanna Matheson; Hermann-Josef Thierse; James Truax; Jens T. Vanselow; Matthias Herzler (Archives of Toxicology, 2023)
Critical to the evaluation of non-animal tests are reference data with which to assess their relevance. Animal data are typically used because they are generally standardized and available. However, when regulatory agencies aim to protect human health, human reference data provide the benefit of not having to account for possible interspecies variability. To support the evaluation of non-animal approaches for skin sensitization assessment, we collected data from 2277 human predictive patch tests (HPPTs), i.e., human repeat insult patch tests and human maximization tests, for skin sensitization from 1555 publications. We recorded protocol elements and positive or negative outcomes, developed a scoring system to evaluate each test for reliability, and calculated traditional and non-traditional dose metrics. We also traced each test result back to its original report to remove duplicates. The resulting database, which contains information for 1366 unique substances, was characterized for physicochemical properties, chemical structure categories, and protein binding mechanisms. This database is publicly available on the National Toxicology Program Interagency Center for the Evaluation of Alternative Toxicological Methods website and in the Integrated Chemical Environment to serve as a resource for additional evaluation of alternative methods and development of new approach methodologies for skin sensitization assessments.

Why humans kill animals and why we cannot avoid it - Benjamin L. Allen; Christopher Bobier; Stuart Dawson; Peter J.S. Fleming; Jordan Hampton; David Jachowski; Graham I.H. Kerley; John D.C. Linnell; Kelly Marnewick; Liaan Minnie; Mike Muthersbaugh; M. Justin O'Riain; et al. (Science of The Total Environment, 2023)

Prioritize rapidly scalable methane reductions in efforts to mitigate climate change - Jennifer B. Dunn; Santiago D. Salas; Qining Chen; David T. Allen (Clean Technologies and Environmental Policy, 2023)
Methane emission reductions are crucial for addressing climate change. It offers short-term benefits as it holds high short-term reductions in radiative forcing. Efforts towards the reduction of methane emissions are already underway. In this study, we compared and analyzed the mitigation benefits of cutting large amounts of methane emissions from the oil and gas sector on short-time scales with reducing an equivalent amount of carbon dioxide using carbon capture and storage (CCS). Characteristics of CCS are that it would require substantial infrastructure development and that it incorporates deployment delays. Results illustrate that prioritizing quickly deployable methane emission reduction alternatives that necessitate minimal construction is an efficient approach to achieve near-term climate change relief. Graphical abstract

Structural asymmetry in biotic interactions as a tool to understand and predict ecological persistence - Alfonso Allen‐Perkins; David García‐Callejas; Ignasi Bartomeus; Oscar Godoy (Ecology Letters, 2023)
A universal feature of ecological systems is that species do not interact with others with the same sign and strength. Yet, the consequences of this asymmetry in biotic interactions for the short‐ and long‐term persistence of individual species and entire communities remains unclear. Here, we develop a set of metrics to evaluate how asymmetric interactions among species translate to asymmetries in their individual vulnerability to extinction under changing environmental conditions. These metrics, which solve previous limitations of how to independently quantify the size from the shape of the so‐called feasibility domain, provide rigorous advances to understand simultaneously why some species and communities present more opportunities to persist than others. We further demonstrate that our shape‐related metrics are useful to predict short‐term changes in species' relative abundances during 7 years in a Mediterranean grassland. Our approach is designed to be applied to any ecological system regardless of the number of species and type of interactions. With it, we show that is possible to obtain both mechanistic and predictive information on ecological persistence for individual species and entire communities, paving the way for a stronger integration of theoretical and empirical research.

Using citizen science to understand floating plastic debris distribution and abundance: A case study from the North Cornish coast (United Kingdom) - Liz Clark; Rebecca Allen; Zara L.R. Botterell; Beatriz Callejo; Brendan J. Godley; Clare Henry; David Santillo; Sarah E. Nelms (Marine Pollution Bulletin, 2023)

Evolution of the Palaeozoic mafic-ultramafic Lizard Complex (SW England) from zircon and baddeleyite U-Pb-Hf isotopic constraints: New thoughts on the convergence of Avalonia and Armorica - Allen P. Nutman; Vickie C. Bennett; David H. Green; Clark R.L. Friend (Lithos, 2023)

Rotation-age effects of subsoiling, fertilization, and weed control on radiata pine growth at sites with contrasting soil physical, nutrient, and water limitations - Rafael Rubilar; Daniel Bozo; Timothy Albaugh; Rachel Cook; Otávio Campoe; David Carter; H. Lee Allen; José Álvarez; Matías Pincheira; Álvaro Zapata (Forest Ecology and Management, 2023)

The Clacton-on-Sea (Essex, UK) GCR site and SSSI: New data and continuing importance - Tom S. White; David R. Bridgland; Peter Allen; Mark J. White (Proceedings of the Geologists' Association, 2023)

Quaternary Earth-science and Palaeolithic conservation initiatives in the Tejo (Tagus), Portugal: Comparison with the Lower Thames, UK - Pedro Proença Cunha; David R. Bridgland; Silvério Figueiredo; António A. Martins; Peter Allen; Mark J. White (Proceedings of the Geologists' Association, 2023)

Reductive metabolism of azo dyes and drugs: Toxicological implications - P. David Josephy; Emma Allen-Vercoe (Food and Chemical Toxicology, 2023)

Who benefits most from a prenatal HEPA filter air cleaner intervention on childhood cognitive development? The UGAAR randomized controlled trial - Battsetseg Ulziikhuu; Enkhjargal Gombojav; Chimeglkham Banzrai; Sarangerel Batsukh; Enkhtuul Enkhtuya; Buyantushig Boldbaatar; David C. Bellinger; Bruce P. Lanphear; Lawrence C. McCandless; Pablo Nepomnaschy; Katrina Salvante; Joanne Weinberg; et al. (Environmental Research, 2023)

Targeting mitochondria in the aged cerebral vasculature with SS-31, a proteomic study of brain microvessels - Abigail Seman; Partha K. Chandra; Stephanie D. Byrum; Samuel G. Mackintosh; Allen J. Gies; David W. Busija; Ibolya Rutkai (GeroScience, 2023)
Cognitive impairment and dementias during aging such as Alzheimer’s disease are linked to functional decline and structural alterations of the brain microvasculature. Although mechanisms leading to microvascular changes during aging are not clear, loss of mitochondria, and reduced efficiency of remaining mitochondria appear to play a major role. Pharmacological agents, such as SS-31, which target mitochondria have been shown to be effective during aging and diseases; however, the benefit to mitochondrial- and non-mitochondrial proteins in the brain microvasculature has not been examined. We tested whether attenuation of aging-associated changes in the brain microvascular proteome via targeting mitochondria represents a therapeutic option for the aging brain. We used aged male (> 18 months) C57Bl6/J mice treated with a mitochondria-targeted tetrapeptide, SS-31, or vehicle saline. Cerebral blood flow (CBF) was determined using laser speckle imaging during a 2-week treatment period. Then, isolated cortical microvessels (MVs) composed of end arterioles, capillaries, and venules were used for Orbitrap Eclipse Tribrid mass spectrometry. CBF was similar among the groups, whereas bioinformatic analysis revealed substantial differences in protein abundance of cortical MVs between SS-31 and vehicle. We identified 6267 proteins, of which 12% were mitochondria-associated. Of this 12%, 107 were significantly differentially expressed and were associated with oxidative phosphorylation, metabolism, the antioxidant defense system, or mitochondrial dynamics. Administration of SS-31 affected many non-mitochondrial proteins. Our findings suggest that mitochondria in the microvasculature represent a therapeutic target in the aging brain, and widespread changes in the proteome may underlie the rejuvenating actions of SS-31 in aging.

Radiogenic Pb in xenotime trapped in nanoscale inclusions of apatite during fluid alteration - Cilva Joseph; Denis Fougerouse; Steven M. Reddy; Hugo K.H. Olierook; Tommaso Tacchetto; Allen Kennedy; David W. Saxey; William D.A. Rickard; Steven Denyszyn; Aaron Dodd (Chemical Geology, 2023)

Amide- and bis-amide-linked highly potent and broadly active antifungal agents for the treatment of invasive fungal infections- towards the discovery of pre-clinical development candidate FC12406 - Simon D. P. Baugh; Anna Chaly; Damian G. Weaver; David B. Whitman; Jeffrey C. Pelletier; Haiyan Bian; Katie B. Freeman; Allen B. Reitz; Richard W. Scott (Medicinal Chemistry Research, 2023)

Panarchy theory for convergence - Shana M. Sundstrom; David G. Angeler; Jesse Bell; Michael Hayes; Jennifer Hodbod; Babak Jalalzadeh-Fard; Rezaul Mahmood; Elizabeth VanWormer; Craig R. Allen (Sustainability Science, 2023)

Non‐random interactions within and across guilds shape the potential to coexist in multi‐trophic ecological communities - David García‐Callejas; Oscar Godoy; Lisa Buche; María Hurtado; Jose B. Lanuza; Alfonso Allen‐Perkins; Ignasi Bartomeus (Ecology Letters, 2023)
Theory posits that the persistence of species in ecological communities is shaped by their interactions within and across trophic guilds. However, we lack empirical evaluations of how the structure, strength and sign of biotic interactions drive the potential to coexist in diverse multi‐trophic communities. Here, we model community feasibility domains, a theoretically informed measure of multi‐species coexistence probability, from grassland communities comprising more than 45 species on average from three trophic guilds (plants, pollinators and herbivores). Contrary to our hypothesis, increasing community complexity, measured either as the number of guilds or community richness, did not decrease community feasibility. Rather, we observed that high degrees of species self‐regulation and niche partitioning allow for maintaining larger levels of community feasibility and higher species persistence in more diverse communities. Our results show that biotic interactions within and across guilds are not random in nature and both structures significantly contribute to maintaining multi‐trophic diversity.

Understanding the global warming potential of circular design strategies: Life cycle assessment of a design-for-disassembly building - Matthew Roberts; Stephen Allen; Joanna Clarke; Justin Searle; David Coley (Sustainable Production and Consumption, 2023)

A framework for functional fish passage decision-making - Rebecca Dolson; R. Allen Curry; Philip M. Harrison; Gordon Yamazaki; Tommi Linnansaari; Mark MacNevin; David L. G. Noakes (Environmental Biology of Fishes, 2023)

The bioeconomic paradox of market-based invasive species harvest: a case study of the commercial lionfish fishery - Holden E. Harris; William F. Patterson; Robert N. M. Ahrens; Micheal S. Allen; David D. Chagaris; Sherry L. Larkin (Biological Invasions, 2023)

Evaluation of the fish acute toxicity test for pesticide registration - Patricia Ceger; David Allen; Amy Blankinship; Neepa Choksi; Amber Daniel; William P. Eckel; Jon Hamm; D. Ethan Harwood; Tamara Johnson; Nicole Kleinstreuer; Catherine S. Sprankle; James Truax; et al. (Regulatory Toxicology and Pharmacology, 2023)

Resilience theory and coerced resilience in agriculture - Shana M. Sundstrom; David G. Angeler; Craig R. Allen (Agricultural Systems, 2023)

Automatic multi-weigh-station for assessing sheep liveweight in small flocks - Harvey Bates; Dougal Pottie; David Taylor; Allen Benter (Computers and Electronics in Agriculture, 2023)

Evaluation of aqueous magnesium concentration on performance of Pacific white shrimp (Litopenaeus vannamei) cultured in low salinity water of West Alabama, USA - David P. Hernández; Hisham A. Abdelrahman; Harsha S.C. Galkanda-Arachchige; Anita M. Kelly; Ian A.E. Butts; D. Allen Davis; Benjamin H. Beck; Luke A. Roy (Aquaculture, 2023)

Sensitivity of solar-induced fluorescence to spectral stray light in high resolution imaging spectroscopy - Loren P. Albert; K.C. Cushman; Yuqin Zong; David W. Allen; Luis Alonso; James R. Kellner (Remote Sensing of Environment, 2023)

Unravelling the synergism of catalytic oxidation and filtration in Co-Mn-oxide impregnated ceramic membrane for intensified degradation of recalcitrant micropollutant with peroxymonosulfate - Arvin Liangdy; Wen Jie Lee; Panyawut Tonanon; Richard David Webster; Shane Allen Snyder; Teik-Thye Lim (Chemical Engineering Journal, 2023)

Development and Evaluation of High-Density SNP Arrays for the Eastern Oyster Crassostrea virginica - Ximing Guo; Jonathan B. Puritz; Zhenwei Wang; Dina Proestou; Standish Allen; Jessica Small; Klara Verbyla; Honggang Zhao; Jaime Haggard; Noah Chriss; Dan Zeng; Kathryn Lundgren; et al. (Marine Biotechnology, 2023)

RecruitNet : A global database of plant recruitment networks - Miguel Verdú; Jose L. Garrido; Julio M. Alcántara; Alicia Montesinos‐Navarro; Salomón Aguilar; Marcelo A. Aizen; Ali A. Al‐Namazi; Mohamed Alifriqui; David Allen; Kristina J. Anderson‐Teixeira; Cristina Armas; Jesús M. Bastida; et al. (Ecology, 2023)
Plant recruitment interactions (i.e., what recruits under what) shape the composition, diversity, and structure of plant communities. Despite the huge body of knowledge on the mechanisms underlying recruitment interactions among species, we still know little about the structure of the recruitment networks emerging in ecological communities. Modeling and analyzing the community‐level structure of plant recruitment interactions as a complex network can provide relevant information on ecological and evolutionary processes acting both at the species and ecosystem levels. We report a data set containing 143 plant recruitment networks in 23 countries across five continents, including temperate and tropical ecosystems. Each network identifies the species under which another species recruits. All networks report the number of recruits (i.e., individuals) per species. The data set includes >850,000 recruiting individuals involved in 118,411 paired interactions among 3318 vascular plant species across the globe. The cover of canopy species and open ground is also provided. Three sampling protocols were used: (1) The Recruitment Network (RN) protocol (106 networks) focuses on interactions among established plants (“canopy species”) and plants in their early stages of recruitment (“recruit species”). A series of plots was delimited within a locality, and all the individuals recruiting and their canopy species were identified; (2) The paired Canopy‐Open (pCO) protocol (26 networks) consists in locating a potential canopy plant and identifying recruiting individuals under the canopy and in a nearby open space of the same area; (3) The Georeferenced plot (GP) protocol (11 networks) consists in using information from georeferenced individual plants in large plots to infer canopy‐recruit interactions. Some networks incorporate data for both herbs and woody species, whereas others focus exclusively on woody species. The location of each study site, geographical coordinates, country, locality, responsible author, sampling dates, sampling method, and life habits of both canopy and recruit species are provided. This database will allow researchers to test ecological, biogeographical, and evolutionary hypotheses related to plant recruitment interactions. There are no copyright restrictions on the data set; please cite this data paper when using these data in publications.

Physiological response of channel (Ictalurus punctatus) and hybrid (I. punctatus x I. furcatus) catfish following Bolbophorus damnificus infection - Mackenzie A. Gunn; Matt J. Griffin; Brian D. Ott; T. Graham Rosser; Lester H. Khoo; David J. Wise; Peter J. Allen (Aquaculture, 2023)

Growth and evolution of NE Australian continental crust interpreted from complex melting-hybridization histories of northern Queensland granulite xenoliths - David T. Murphy; Robert Emo; Blake Deegan; Charlotte Allen (Gondwana Research, 2023)

Cover Image - Rachel N. Hofer; Allen Lin; Benjamin C. House; Christopher N. Purvis; Bradley J. Harris; Steven J. K. Symes; David K. Giles (Journal of Fish Diseases, 2023)

Exogenous polyunsaturated fatty acids ( PUFAs ) influence permeability, antimicrobial peptide resistance, biofilm formation and membrane phospholipid structure in an A‐layer and non‐A ‐layer strain of Aeromonas salmonicida - Rachel N. Hofer; Allen Lin; Benjamin C. House; Christopher N. Purvis; Bradley J. Harris; Steven J. K. Symes; David K. Giles (Journal of Fish Diseases, 2023)
Aeromonas salmonicida is a Gram‐negative bacterium that can infect a wide host range of fish populations, including salmonids and non‐salmonids as well as freshwater and marine life. Some strains of A. salmonicida cause the disease furunculosis, which can cause lethargy, intestinal inflammation, ulcers, haemorrhaging and death. The infection is spread through fish‐to‐fish contact, and the presence of infection can have devastating effects on cultivated fish populations. The purpose of this study was to explore the ability of non‐A‐layer and A‐layer A. salmonicida strains to incorporate polyunsaturated fatty acids (PUFAs) into their lipid profile and test the phenotypic effects thereof. Lipids were extracted from PUFA‐exposed cultures and analysed for lipid modification by thin‐layer chromatography and ultraperformance liquid chromatography‐mass spectrometry, showing A. salmonicida , regardless of A‐layer, capable of incorporating all seven of the PUFAs studied. Phenotypic effects were determined through the use of assays that tested for biofilm formation, membrane permeability and cyclic peptide susceptibility. Temperature‐dependent effects on biofilm formation were observed, and PUFA exposure showed significant ( p

A novel method for identifying coded tags recorded on aquatic acoustic monitoring systems - Christopher D. Lowe; Nicolas J. C. Tregenza; Claudia J. Allen; Georgina E. Blow; Hanna Nuuttila; Chiara M. Bertelli; Anouska F. Mendzil; Thomas Stamp; Emma V. Sheehan; Peter Davies; Jonathan C. D. Gordon; Jonathan D. Bolland; et al. (Environmental Monitoring and Assessment, 2022)
Aquatic biotelemetry increasingly relies on using acoustic transmitters (‘tags’) that enable passive detection of tagged animals using fixed or mobile receivers. Both tracking methods are resource-limited, restricting the spatial area in which movements of highly mobile animals can be measured using proprietary detection systems. Transmissions from tags are recorded by underwater noise monitoring systems designed for other purposes, such as cetacean monitoring devices, which have been widely deployed in the marine environment; however, no tools currently exist to decode these detections, and thus valuable additional information on animal movements may be missed. Here, we describe simple hybrid methods, with potentially wide application, for obtaining information from otherwise unused data sources. The methods were developed using data from moored, acoustic cetacean detectors (C-PODs) and towed passive receiver arrays, often deployed to monitor the vocalisations of cetaceans, but any similarly formatted data source could be used. The method was applied to decode tag detections that were found to have come from two highly mobile fish species, bass ( Dicentrarchus labrax ) and Twaite shad ( Alosa fallax ), that had been tagged in other studies. Decoding results were validated using test tags; range testing data were used to demonstrate the relative efficiency of these receiver methods in detecting tags. This approach broadens the range of equipment from which acoustic tag detections can be decoded. Novel detections derived from the method could add significant value to past and present tracking studies at little additional cost, by providing new insights into the movement of mobile animals at sea.

An integrated approach to assessing abiotic and biotic threats to post‐fire plant species recovery: Lessons from the 2019–2020 Australian fire season - Rachael V. Gallagher; Stuart P. Allen; Berin D. E. Mackenzie; David A. Keith; Rachael H. Nolan; Libby Rumpff; Carl R. Gosper; Geoffrey Pegg; Stephen van Leeuwen; Mark K. J. Ooi; Colin J. Yates; Cory Merow; et al. (Global Ecology and Biogeography, 2022)
Aim Existing abiotic and biotic threats to plant species (e.g., disease, drought, invasive species) affect their capacity to recover post‐fire. We use a new, globally applicable framework to assess the vulnerability of 26,062 Australian plant species to a suite of active threats after the 2019–2020 fires. Location Australia. Time period 2019–2020. Major species studied Plants. Methods Spatial data for existing threats and information on species‐level susceptibility were combined with estimates of the extent of range burnt in southern Australia (> 22°S) to assign species against 10 criteria into vulnerability categories ( high , medium , low , none , data deficient ). We explore in detail results for three threats (drought, disease, feral animals), highlighting where impacts from multiple threats ranked high vulnerability may compound to reduce post‐fire recovery. Results Analysis of the full suite of 10 vulnerability criteria, which encompass a broad range of threats, revealed large numbers of species vulnerable to poor post‐fire recovery from one or more different hazards ( high vulnerability: 1,243 species; medium vulnerability: 2,450 species). Collectively, 457 plant species that burnt extensively (> 50%) across their range are highly vulnerable to poor recovery due to exposure to pre‐fire drought conditions (235 species), disease (186 species), or feral animals (97 species). Of these 457 species, 61 are vulnerable to more than one of these three threats, highlighting how a suite of interacting hazards can impact plant recovery after fire. Main conclusions While fire can renew plant populations by stimulating recruitment and resetting competitive interactions, the presence of existing threats in post‐fire landscapes jeopardizes recovery. The simultaneous impact of multiple threats that impact recovery can create a suite of hazards that contribute to declines and, potentially, extinction. Our method for rapid post‐fire vulnerability assessment can be applied to large numbers of plant species or other biota in fire affected regions globally.

Fire‐related threats and transformational change in Australian ecosystems - David A. Keith; Stuart P. Allen; Rachael V. Gallagher; Berin D. E. Mackenzie; Tony D. Auld; Sarah Barrett; Anne Buchan; Valerie English; Carl Gosper; Dave Kelly; Allen McIllwee; Rachel T. Melrose; et al. (Global Ecology and Biogeography, 2022)
Aim Megafire events generate immediate concern for wildlife and human well‐being, but their broader ecological impacts likely extend beyond individual species and single fire events. In the first mechanistic study of fire effects focussed on ecosystems, we aimed to assess the sensitivity and exposure of ecosystems to multiple fire‐related threats, placing impacts in the context of changing fire regimes and their interactions with other threats. Location Southern and eastern Australia. Time period 2019–2020. Major species studied Australian ecosystems. Methods We defined 15 fire‐related threats to ecosystems based on mechanisms associated with: (a) direct effects of fire regime components; (b) interactions between fire and physical environmental processes; (c) effects of fire on biological interactions; and (d) interactions between fire and human activity. We estimated the sensitivity and exposure of a sample of 92 ecosystem types to each threat type based on published relationships and spatial analysis of the 2019–2020 fires. Results Twenty‐nine ecosystem types assessed had more than half of their distribution exposed to one or more threat types, and only three of those were listed as nationally threatened. Three fire‐related threat types posed the most severe threats to large numbers of ecosystem types: high frequency fire; pre‐fire drought; and post‐fire invasive predator activity. The ecosystem types most affected ranged from rain forests to peatlands, and included some, such as sclerophyllous eucalypt forests and heathlands, that are traditionally regarded as fire‐prone and fire‐adapted. Main conclusions Most impacts of the 2019–2020 fires on ecosystems became apparent only when they were placed in the context of the whole fire regime and its interactions with other threatening processes, and were not direct consequences of the megafire event itself. Our mechanistic approach enables ecosystem‐specific management responses for the most threatened ecosystem types to be targeted at underlying causes of degradation and decline.

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Plankton Planet: A frugal, cooperative measure of aquatic life at the planetary scale - Colomban de Vargas; Noan Le Bescot; Thibaut Pollina; Nicolas Henry; Sarah Romac; Sébastien Colin; Nils Haëntjens; Margaux Carmichael; Calixte Berger; David Le Guen; Johan Decelle; Frédéric Mahé; et al. (Frontiers in Marine Science, 2022)
In every liter of seawater there are between 10 and 100 billion life forms, mostly invisible, called marine plankton or marine microbiome, which form the largest and most dynamic ecosystem on our planet, at the heart of global ecological and economic processes. While physical and chemical parameters of planktonic ecosystems are fairly well measured and modeled at the planetary scale, biological data are still scarce due to the extreme cost and relative inflexibility of the classical vessels and instruments used to explore marine biodiversity. Here we introduce ‘Plankton Planet’, an initiative whose goal is to engage the curiosity and creativity of researchers, makers, and mariners to ( i ) co-develop a new generation of cost-effective (frugal) universal scientific instrumentation to measure the genetic and morphological diversity of marine microbiomes in context, ( ii ) organize their systematic deployment through coastal or open ocean communities of sea-users/farers, to generate uniform plankton data across global and long-term spatio-temporal scales, and ( iii ) setup tools to flow the data without embargo into public and explorable databases. As proof-of-concept, we show how 20 crews of sailors were able to sample plankton biomass from the world surface ocean in a single year, generating the first seatizen-based, planetary dataset of marine plankton biodiversity based on DNA barcodes. The quality of this dataset is comparable to that generated by Tara Oceans and is not biased by the multiplication of samplers. The data unveil significant genetic novelty and can be used to explore the taxonomic and ecological diversity of plankton at both regional and global scales. This pilot project paves the way for construction of a miniaturized, modular, evolvable, affordable and open-source citizen field-platform that will allow systematic assessment of the eco/morpho/genetic variation of aquatic ecosystems and microbiomes across the dimensions of the Earth system.

Innovating the Blue Economy: A Novel Approach to Stakeholder Landscape Mapping of the Atlantic Area Sea Basin - Daniel Depellegrin; Aleksandra Zawalna-Geer; Allen Alexander; David Rodeiro-Pazos; Adrian Dios-Vicente; Boris Teillant; Amita Guneratman; Kate Hogan; Emanuel Mendonça; Ian Ashton; Lars Johanning (Frontiers in Marine Science, 2022)
The Blue Economy is an emerging paradigm with the potential to foster balanced socio-economic development of the world’s oceans and coastal areas, but it requires an understanding of the stakeholder landscape at a national and at an international sea basin scale, so that we can model potential equitable and collaborative economic development. Applying a novel, mixed-method approach we collected, collated and analysed spatial and non-spatial stakeholder information from five countries (United Kingdom, Ireland, France, Spain and Portugal), that border the North East Atlantic sea basin. Through the development of Blue Economy stakeholder directory for the North East Atlantic area more than 600 local, regional, national and international (EU wide and global) stakeholders were analysed in terms of their Blue Economy alignment and to determine their respective enabling role (financier, service providers, research/innovators and regulators/policy makers). Results show 72% of the North East Atlantic sea basin stakeholders fail to recognise the socio-economic potential of the Blue Economy, regardless of the new policy instruments and a strategic focus from the European Commission. We also identify that public and research/academic institutions currently dominate the landscape of Blue Economy stakeholders; but note this is inconsistent, when compared with other economic sectors in maritime territories. Based on the results, we discuss the key challenges facing equitable growth of the Blue Economy in the North East Atlantic area.

Predicting Seabird Foraging Habitat for Conservation Planning in Atlantic Canada: Integrating Telemetry and Survey Data Across Thousands of Colonies - Robert A. Ronconi; David J. Lieske; Laura A. McFarlane Tranquilla; Sue Abbott; Karel A. Allard; Brad Allen; Amie L. Black; François Bolduc; Gail K. Davoren; Antony W. Diamond; David A. Fifield; Stefan Garthe; et al. (Frontiers in Marine Science, 2022)
Conservation of mobile organisms is difficult in the absence of detailed information about movement and habitat use. While the miniaturization of tracking devices has eased the collection of such information, it remains logistically and financially difficult to track a wide range of species across a large geographic scale. Predictive distribution models can be used to fill this gap by integrating both telemetry and census data to construct distribution maps and inform conservation goals and planning. We used tracking data from 520 individuals of 14 seabird species in Atlantic Canada to first compare foraging range and distance to shorelines among species across colonies, and then developed tree-based machine-learning models to predict foraging distributions for more than 5000 breeding sites distributed along more than 5000 km of shoreline. Despite large variability in foraging ranges among species, tracking data revealed clusters of species using similar foraging habitats (e.g., nearshore vs. offshore foragers), and within species, foraging range was highly colony-specific. Even with this variability, distance from the nesting colony was an important predictor of distribution for nearly all species, while distance from coastlines and bathymetry (slope and ruggedness) were additional important predictors for some species. Overall, we demonstrated the utility of tree-based machine-learning approach when modeling tracking data to predict distributions at un-sampled colonies. Although tracking and colony data have some shortcomings (e.g., fewer data for some species), where results need to be interpreted with care in some cases, applying methods for modeling breeding season distributions of seabirds allows for broader-scale conservation assessment. The modeled distributions can be used in decisions about planning for offshore recreation and commercial activities and to inform conservation planning at regional scales.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Passive-Sampler-Based Bioavailability Assessment of PCB Congeners Associated with Aroclor-Containing Paint Chips in the Presence of Sediment - Guilherme R. Lotufo; Philip T. Gidley; Andrew D. McQueen; David W. Moore; Deborah A. Edwards; Jeffery Hardenstine; Allen D. Uhler (Archives of Environmental Contamination and Toxicology, 2022)
This is the first investigation of the bioavailability of PCBs associated with paint chips (PC) dispersed in sediment. Bioavailability of PCB-containing PC in sediment was measured using ex situ polyethylene passive samplers (PS) and compared to that of PCBs from field-collected sediments. PC were mixed in freshwater sediment from a relatively uncontaminated site with no known PCB contamination sources and from a contaminated site with non-paint PCB sources. PC

Adherence to Mammography and Pap Screening Guidelines Among Medically Underserved Women: the Role of Family Structures and Network-Level Behaviors - Caitlin G. Allen; David Todem; Karen Patricia Williams (Journal of Cancer Education, 2021)

Functional traits driving species role in the structure of terrestrial vertebrate scavenger networks - Esther Sebastián‐González; Zebensui Morales‐Reyes; Francisco Botella; Lara Naves‐Alegre; Juan M. Pérez‐García; Patricia Mateo‐Tomás; Pedro P. Olea; Marcos Moleón; Jomar Magalhães Barbosa; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; et al. (Ecology, 2021)
Species assemblages often have a non‐random nested organization, which in vertebrate scavenger (carrion‐consuming) assemblages is thought to be driven by facilitation in competitive environments. However, not all scavenger species play the same role in maintaining assemblage structure, as some species are obligate scavengers (i.e., vultures) and others are facultative, scavenging opportunistically. We used a database with 177 vertebrate scavenger species from 53 assemblages in 22 countries across five continents to identify which functional traits of scavenger species are key to maintaining the scavenging network structure. We used network analyses to relate ten traits hypothesized to affect assemblage structure with the “role” of each species in the scavenging assemblage in which it appeared. We characterized the role of a species in terms of both the proportion of monitored carcasses on which that species scavenged, or scavenging breadth (i.e., the species “normalized degree”), and the role of that species in the nested structure of the assemblage (i.e., the species “paired nested degree”), therefore identifying possible facilitative interactions among species. We found that species with high olfactory acuity, social foragers, and obligate scavengers had the widest scavenging breadth. We also found that social foragers had a large paired nested degree in scavenger assemblages, probably because their presence is easier to detect by other species to signal carcass occurrence. Our study highlights differences in the functional roles of scavenger species and can be used to identify key species for targeted conservation to maintain the ecological function of scavenger assemblages.

Anticipating and Adapting to the Future Impacts of Climate Change on the Health, Security and Welfare of Low Elevation Coastal Zone (LECZ) Communities in Southeastern USA - Thomas Allen; Joshua Behr; Anamaria Bukvic; Ryan S. D. Calder; Kiki Caruson; Charles Connor; Christopher D’Elia; David Dismukes; Robin Ersing; Rima Franklin; Jesse Goldstein; Jonathon Goodall; et al. (Journal of Marine Science and Engineering, 2021)
Low elevation coastal zones (LECZ) are extensive throughout the southeastern United States. LECZ communities are threatened by inundation from sea level rise, storm surge, wetland degradation, land subsidence, and hydrological flooding. Communication among scientists, stakeholders, policy makers and minority and poor residents must improve. We must predict processes spanning the ecological, physical, social, and health sciences. Communities need to address linkages of (1) human and socioeconomic vulnerabilities; (2) public health and safety; (3) economic concerns; (4) land loss; (5) wetland threats; and (6) coastal inundation. Essential capabilities must include a network to assemble and distribute data and model code to assess risk and its causes, support adaptive management, and improve the resiliency of communities. Better communication of information and understanding among residents and officials is essential. Here we review recent background literature on these matters and offer recommendations for integrating natural and social sciences. We advocate for a cyber-network of scientists, modelers, engineers, educators, and stakeholders from academia, federal state and local agencies, non-governmental organizations, residents, and the private sector. Our vision is to enhance future resilience of LECZ communities by offering approaches to mitigate hazards to human health, safety and welfare and reduce impacts to coastal residents and industries.

High Throughput Argon-37 Field System - James C. Hayes; Craig Aalseth; Thomas Alexander; Henning Back; Eric Church; Michael Foxe; Todd Hossbach; Paul Humble; Lance Lidey; Emily Mace; Kerry Meinhardt; Jennifer Mendez; et al. (Pure and Applied Geophysics, 2021)

The conservation status of the world’s freshwater molluscs - Monika Böhm; Nadia I. Dewhurst-Richman; Mary Seddon; Sophie E. H. Ledger; Christian Albrecht; David Allen; Arthur E. Bogan; Jay Cordeiro; Kevin S. Cummings; Annabelle Cuttelod; Gustavo Darrigran; Will Darwall; et al. (Hydrobiologia, 2021)

Exploring Impacts of River Discharge on Forage Fish and Predators Using Ecopath With Ecosim - Dylan Sinnickson; David Chagaris; Micheal Allen (Frontiers in Marine Science, 2021)
The ecology of estuaries is shaped significantly by the extent of freshwater discharge which regulates abiotic processes and influences overall biological productivity. The Suwannee River Estuary of Florida’s Big Bend Coastline has historically been a productive and diverse estuarine ecosystem supported by significant freshwater inputs from the Suwannee River. In recent years, significant changes in land use and climatic conditions have resulted in lower discharges from the Suwannee. Our objectives were to explore the impact of freshwater inputs from the Suwannee River on the estuarine forage fish and sportfish communities downstream. We built a trophic-dynamic food web model in Ecopath with Ecosim to simulate different levels of discharge and evaluate how changes in discharge (drought and floods) would influence the trophic structure of the food web. Using the fitted model, we applied a series of different short-term and long-term flow projections under different climatic scenarios to evaluate impacts on fish functional groups and sportfish biomass. Simulations suggested that ecological production was more influenced by drought conditions than flood conditions. In our short-term scenarios, the drought simulations produced biomass changes that were approximately twice as substantial as the flood scenarios. When making comparisons to other published EwE models, we generally observed smaller changes in biomass production. Although this model focused on the influence of bottom-up effects, we observed strong top-down control of snook ( Centropomus undecimalis ) on the system. Several functional groups were particularly sensitive to changes in snook abundance which included spotted seatrout ( Cynoscion nebulosus ), sand seatrout ( C. arenarius ), and other members of the family Sciaenidae . Because snook have recently colonized the estuary, likely as a result of warmer winter temperatures, this finding has implications for climate change and natural resource management.

Skeletal muscle mitochondrial DNA copy number and mitochondrial DNA deletion mutation frequency as predictors of physical performance in older men and women - Allen Herbst; Steven J. Prior; Cathy C. Lee; Judd M. Aiken; Debbie McKenzie; Austin Hoang; Nianjun Liu; Xiwei Chen; Pengcheng Xun; David B. Allison; Jonathan Wanagat (GeroScience, 2021)

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Implementation of a Medication for Addiction Treatment (MAT) and Linkage Program by Leveraging Community Partnerships and Medical Toxicology Expertise - Gillian A. Beauchamp; Lexis T. Laubach; Samantha B. Esposito; Ali Yazdanyar; Paige Roth; Priyanka Lauber; Jamie Allen; Nathan Boateng; Samantha Shaak; David B. Burmeister (Journal of Medical Toxicology, 2021)

Groundwater recharge to a structurally complex aquifer system on the island of Tobago (Republic of Trinidad and Tobago) - David F. Boutt; Marsha Allen; Mark Settembrino; Amber Bonarigo; Joseph Ingari; Rose Demars; Lee Ann Munk (Hydrogeology Journal, 2021)

Screening for Ralstonia solanacearum Resistance in Solanum commersonii - Susan A. Otieno; Paul Collins; Joseph Coombs; Caitlyn Allen; David S Douches (American Journal of Potato Research, 2021)

A 50-Year Retrospective of the Forest Productivity Cooperative in the Southeastern United States: Regionwide Trials - David R Carter; H Lee Allen; Thomas R Fox; Timothy J Albaugh; Rafael A Rubilar; Otávio C Campoe; Rachel L Cook (Journal of Forestry, 2021)
In 2019, the Forest Productivity Cooperative (FPC) celebrated its 50th anniversary. The mission of the FPC is and has been creating innovative solutions to enhance forest productivity and value through the sustainable management of site resources. This industry-government-university partnership has generated seminal research with sweeping implications for increasing productivity throughout the southeastern United States and Latin America. To commemorate this semicentennial, we highlighted some of the pivotal findings in the southeastern United States from the past 50 years derived from our large, regional experiments: regionwide trials.

Association of HIV serostatus and metabolic syndrome with neurobehavioral disturbances - Caitlin N. Pope; Jessica L. Montoya; Elizabeth Vasquez; Josué Pérez-Santiago; Ronald Ellis; J. Allen McCutchan; Dilip V. Jeste; David J. Moore; María J. Marquine (Journal of NeuroVirology, 2020)

Controls on Ocean Color Spectra Observed During the North Atlantic Aerosols and Marine Ecosystems Study (NAAMES) - James G. Allen; David A. Siegel; Norman B. Nelson; Stuart Halewood (Frontiers in Marine Science, 2020)

Ensuring tests of conservation interventions build on existing literature - William J. Sutherland; Sergio Ticul Alvarez‐Castañeda; Tatsuya Amano; Roberto Ambrosini; Philip Atkinson; John M. Baxter; Alexander L. Bond; Philip J. Boon; Katherine L. Buchanan; Jos Barlow; Giuseppe Bogliani; Olivia M. Bragg; et al. (Conservation Biology, 2020)

Relative Effects of Multiple Stressors on Reef Food Webs in the Northern Gulf of Mexico Revealed via Ecosystem Modeling - David D. Chagaris; William F. Patterson; Micheal S. Allen (Frontiers in Marine Science, 2020)

Uncertainty in geomorphological responses to climate change - Stephan Harrison; Tim Mighall; David A. Stainforth; Philip Allen; Mark Macklin; Edward Anderson; Jasper Knight; Dmitri Mauquoy; David Passmore; Brice Rea; Matteo Spagnolo; Sarah Shannon (Climatic Change, 2019)

Scavenging in the Anthropocene: Human impact drives vertebrate scavenger species richness at a global scale - Esther Sebastián‐González; Jomar Magalhães Barbosa; Juan M. Pérez‐García; Zebensui Morales‐Reyes; Francisco Botella; Pedro P. Olea; Patricia Mateo‐Tomás; Marcos Moleón; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; Ainara Cortés‐Avizanda; et al. (Global Change Biology, 2019)
Understanding the distribution of biodiversity across the Earth is one of the most challenging questions in biology. Much research has been directed at explaining the species latitudinal pattern showing that communities are richer in tropical areas; however, despite decades of research, a general consensus has not yet emerged. In addition, global biodiversity patterns are being rapidly altered by human activities. Here, we aim to describe large‐scale patterns of species richness and diversity in terrestrial vertebrate scavenger (carrion‐consuming) assemblages, which provide key ecosystem functions and services. We used a worldwide dataset comprising 43 sites, where vertebrate scavenger assemblages were identified using 2,485 carcasses monitored between 1991 and 2018. First, we evaluated how scavenger richness (number of species) and diversity (Shannon diversity index) varied among seasons (cold vs. warm, wet vs. dry). Then, we studied the potential effects of human impact and a set of macroecological variables related to climatic conditions on the scavenger assemblages. Vertebrate scavenger richness ranged from species‐poor to species rich assemblages (4–30 species). Both scavenger richness and diversity also showed some seasonal variation. However, in general, climatic variables did not drive latitudinal patterns, as scavenger richness and diversity were not affected by temperature or rainfall. Rainfall seasonality slightly increased the number of species in the community, but its effect was weak. Instead, the human impact index included in our study was the main predictor of scavenger richness. Scavenger assemblages in highly human‐impacted areas sustained the smallest number of scavenger species, suggesting human activity may be overriding other macroecological processes in shaping scavenger communities. Our results highlight the effect of human impact at a global scale. As species‐rich assemblages tend to be more functional, we warn about possible reductions in ecosystem functions and the services provided by scavengers in human‐dominated landscapes in the Anthropocene.

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Identification and characterization of a novel anti-inflammatory lipid isolated from Mycobacterium vaccae, a soil-derived bacterium with immunoregulatory and stress resilience properties - David G. Smith; Roberta Martinelli; Gurdyal S. Besra; Petr A. Illarionov; Istvan Szatmari; Peter Brazda; Mary A. Allen; Wenqing Xu; Xiang Wang; László Nagy; Robin D. Dowell; Graham A. W. Rook; et al. (Psychopharmacology, 2019)

Placing prostate cancer disparities within a psychosocial context: challenges and opportunities for future research - Adolfo G. Cuevas; Claudia Trudel-Fitzgerald; Leslie Cofie; Masayoshi Zaitsu; Jennifer Allen; David R. Williams (Cancer Causes & Control, 2019)

Quantification of Cerebellar Crowding in Type I Chiari Malformation - Dipankar Biswas; Maggie S. Eppelheimer; James R. Houston; Alaaddin Ibrahimy; J. Rajiv Bapuraj; Richard Labuda; Philip A. Allen; David Frim; Francis Loth (Annals of Biomedical Engineering, 2019)

White matter damage, neuroinflammation, and neuronal integrity in HAND - Aljoharah Alakkas; Ronald J. Ellis; Caitlin Wei-Ming Watson; Anya Umlauf; Robert K. Heaton; Scott Letendre; Ann Collier; Christina Marra; David B. Clifford; Benjamin Gelman; Ned Sacktor; Susan Morgello; et al. (Journal of NeuroVirology, 2019)

Skin sensitization testing needs and data uses by US regulatory and research agencies - Judy Strickland; Amber B. Daniel; David Allen; Cecilia Aguila; Surender Ahir; Simona Bancos; Evisabel Craig; Dori Germolec; Chandramallika Ghosh; Naomi L. Hudson; Abigail Jacobs; David M. Lehmann; et al. (Archives of Toxicology, 2019)

Mātauranga Māori driving innovation in the New Zealand scampi fishery - Shaun Ogilvie; Robert Major; Alaric McCarthy; Glenice Paine; Richard Paine; Geoff Connor; Steve Connor; David Taylor; Andrew Jeffs; Kevin Heasman; Chris Batstone; Benita Chambers; et al. (New Zealand Journal of Marine and Freshwater Research, 2018)
Motivation to improve commercial fishing technology is changing from ‘how can we catch more fish’ to ‘how can we reduce the impact of fishing on the environment’. To implement new fisheries technologies and innovations, it is important to have sources of innovative ideas for improvement, and processes to allow the uptake and transition from old to new technologies. One fishery that is undergoing a technology transition is the New Zealand scampi ( Metanephrops challengeri ) fishery. Here we report on a research programme aimed at improving the cultural and environmental performance of scampi fishing practices, initiated by the Māori‐owned Waikawa Fishing Company, and underpinned by Mātauranga Māori and values inherent in kaitiakitanga. This paper provides a case study for how Mātauranga Māori and western science can engage in a fisheries technology transition through a transdisciplinary research programme.

Resilience in Environmental Risk and Impact Assessment: Concepts and Measurement - David G. Angeler; Craig R. Allen; Ahjond Garmestani; Kevin L. Pope; Dirac Twidwell; Mirco Bundschuh (Bulletin of Environmental Contamination and Toxicology, 2018)

The distribution and role of functional abundance in cross‐scale resilience - Shana M. Sundstrom; David G. Angeler; Chris Barichievy; Tarsha Eason; Ahjond Garmestani; Lance Gunderson; Melinda Knutson; Kirsty L. Nash; Trisha Spanbauer; Craig Stow; Craig R. Allen (Ecology, 2018)
The cross‐scale resilience model suggests that system‐level ecological resilience emerges from the distribution of species’ functions within and across the spatial and temporal scales of a system. It has provided a quantitative method for calculating the resilience of a given system and so has been a valuable contribution to a largely qualitative field. As it is currently laid out, the model accounts for the spatial and temporal scales at which environmental resources and species are present and the functional roles species play but does not inform us about how much resource is present or how much function is provided. In short, it does not account for abundance in the distribution of species and their functional roles within and across the scales of a system. We detail the ways in which we would expect species’ abundance to be relevant to the cross‐scale resilience model based on the extensive abundance literature in ecology. We also put forward a series of testable hypotheses that would improve our ability to anticipate and quantify how resilience is generated, and how ecosystems will (or will not) buffer recent rapid global changes. This stream of research may provide an improved foundation for the quantitative evaluation of ecological resilience.

Kv7 channels are upregulated during striatal neuron development and promote maturation of human iPSC-derived neurons - Vsevolod Telezhkin; Marco Straccia; Polina Yarova; Monica Pardo; Sun Yung; Ngoc-Nga Vinh; Jane M. Hancock; Gerardo Garcia-Diaz Barriga; David A. Brown; Anne E. Rosser; Jonathan T. Brown; Josep M. Canals; et al. (Pflügers Archiv - European Journal of Physiology, 2018)

Consensus guidelines for the use and interpretation of angiogenesis assays - Patrycja Nowak-Sliwinska; Kari Alitalo; Elizabeth Allen; Andrey Anisimov; Alfred C. Aplin; Robert Auerbach; Hellmut G. Augustin; David O. Bates; Judy R. van Beijnum; R. Hugh F. Bender; Gabriele Bergers; Andreas Bikfalvi; et al. (Angiogenesis, 2018)

The perpetual state of emergency that sacrifices protected areas in a changing climate - Dirac Twidwell; Carissa L. Wonkka; Christine H. Bielski; Craig R. Allen; David G. Angeler; Jacob Drozda; Ahjond S. Garmestani; Julia Johnson; Larkin A. Powell; Caleb P. Roberts (Conservation Biology, 2018)
A modern challenge for conservation biology is to assess the consequences of policies that adhere to assumptions of stationarity (e.g., historic norms) in an era of global environmental change. Such policies may result in unexpected and surprising levels of mitigation given future climate‐change trajectories, especially as agriculture looks to protected areas to buffer against production losses during periods of environmental extremes. We assessed the potential impact of climate‐change scenarios on the rates at which grasslands enrolled in the Conservation Reserve Program (CRP) are authorized for emergency harvesting (i.e., biomass removal) for agricultural use, which can occur when precipitation for the previous 4 months is below 40% of the normal or historical mean precipitation for that 4‐month period. We developed and analyzed scenarios under the condition that policy will continue to operate under assumptions of stationarity, thereby authorizing emergency biomass harvesting solely as a function of precipitation departure from historic norms. Model projections showed the historical likelihood of authorizing emergency biomass harvesting in any given year in the northern Great Plains was 33.28% based on long‐term weather records. Emergency biomass harvesting became the norm (>50% of years) in the scenario that reflected continued increases in emissions and a decrease in growing‐season precipitation, and areas in the Great Plains with higher historical mean annual rainfall were disproportionately affected and were subject to a greater increase in emergency biomass removal. Emergency biomass harvesting decreased only in the scenario with rapid reductions in emissions. Our scenario‐impact analysis indicated that biomass from lands enrolled in the CRP would be used primarily as a buffer for agriculture in an era of climatic change unless policy guidelines are adapted or climate‐change projections significantly depart from the current consensus.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Transformation in a changing climate: a research agenda - Ioan Fazey; Peter Moug; Simon Allen; Kate Beckmann; David Blackwood; Mike Bonaventura; Kathryn Burnett; Mike Danson; Ruth Falconer; Alexandre S. Gagnon; Rachel Harkness; Anthony Hodgson; et al. (Climate and Development, 2018)

The development of an in vitro Pig-a assay in L5178Y cells - Rhiannon David; Emily Talbot; Bethany Allen; Amy Wilson; Usman Arshad; Ann Doherty (Archives of Toxicology, 2018)

Metabolomics of tomato xylem sap during bacterial wilt reveals Ralstonia solanacearum produces abundant putrescine, a metabolite that accelerates wilt disease - Tiffany M. Lowe‐Power; Connor G. Hendrich; Edda von Roepenack‐Lahaye; Bin Li; Dousheng Wu; Raka Mitra; Beth L. Dalsing; Patrizia Ricca; Jacinth Naidoo; David Cook; Amy Jancewicz; Patrick Masson; et al. (Environmental Microbiology, 2018)
Summary Ralstonia solanacearum thrives in plant xylem vessels and causes bacterial wilt disease despite the low nutrient content of xylem sap. We found that R. solanacearum manipulates its host to increase nutrients in tomato xylem sap, enabling it to grow better in sap from infected plants than in sap from healthy plants. Untargeted GC/MS metabolomics identified 22 metabolites enriched in R. solanacearum ‐infected sap. Eight of these could serve as sole carbon or nitrogen sources for R. solanacearum . Putrescine, a polyamine that is not a sole carbon or nitrogen source for R. solanacearum , was enriched 76‐fold to 37 µM in R. solanacearum ‐infected sap. R. solanacearum synthesized putrescine via a SpeC ornithine decarboxylase. A Δ speC mutant required ≥ 15 µM exogenous putrescine to grow and could not grow alone in xylem even when plants were treated with putrescine. However, co‐inoculation with wildtype rescued ΔspeC growth, indicating R. solanacearum produced and exported putrescine to xylem sap. Intriguingly, treating plants with putrescine before inoculation accelerated wilt symptom development and R. solanacearum growth and systemic spread. Xylem putrescine concentration was unchanged in putrescine‐treated plants, so the exogenous putrescine likely accelerated disease indirectly by affecting host physiology. These results indicate that putrescine is a pathogen‐produced virulence metabolite.

A review of the associations between single nucleotide polymorphisms in taste receptors, eating behaviors, and health - Elie Chamoun; David M. Mutch; Emma Allen-Vercoe; Andrea C. Buchholz; Alison M. Duncan; Lawrence L. Spriet; Jess Haines; David W. L. Ma (Critical Reviews in Food Science and Nutrition, 2018)

Species distribution model for the ‘Northern’ Oak hairstreak (Satyrium favonius ontario) with comments on its conservation status in the northeastern United States - Benedict L. Gagliardi; David L. Wagner; Jenica M. Allen (Journal of Insect Conservation, 2017)

Erratum to: A multi-stage genome-wide association study of uterine fibroids in African Americans - Jacklyn N. Hellwege; Janina M. Jeff; Lauren A. Wise; C. Scott Gallagher; Melissa Wellons; Katherine E. Hartmann; Sarah F. Jones; Eric S. Torstenson; Scott Dickinson; Edward A. Ruiz-Narváez; Nadin Rohland; Alexander Allen; et al. (Human Genetics, 2017)

A multi-stage genome-wide association study of uterine fibroids in African Americans - Jacklyn N. Hellwege; Janina M. Jeff; Lauren A. Wise; C. Scott Gallagher; Melissa Wellons; Katherine E. Hartmann; Sarah F. Jones; Eric S. Torstenson; Scott Dickinson; Edward A. Ruiz-Narváez; Nadin Rohland; Alexander Allen; et al. (Human Genetics, 2017)
Uterine fibroids are benign tumors of the uterus affecting up to 77% of women by menopause. They are the leading indication for hysterectomy, and account for $34 billion annually in the United States. Race/ethnicity and age are the strongest known risk factors. African American (AA) women have higher prevalence, earlier onset, and larger and more numerous fibroids than European American women. We conducted a multi-stage genome-wide association study (GWAS) of fibroid risk among AA women followed by in silico genetically predicted gene expression profiling of top hits. In Stage 1, cases and controls were confirmed by pelvic imaging, genotyped and imputed to 1000 Genomes. Stage 2 used self-reported fibroid and GWAS data from 23andMe, Inc. and the Black Women’s Health Study. Associations with fibroid risk were modeled using logistic regression adjusted for principal components, followed by meta-analysis of results. We observed a significant association among 3399 AA cases and 4764 AA controls at rs739187 (risk-allele frequency = 0.27) in CYTH4 (OR (95% confidence interval) = 1.23 (1.16–1.30), p value = 7.82 × 10 −9 ). Evaluation of the genetic association results with MetaXcan identified lower predicted gene expression of CYTH4 in thyroid tissue as significantly associated with fibroid risk ( p value = 5.86 × 10 −8 ). In this first multi-stage GWAS for fibroids among AA women, we identified a novel risk locus for fibroids within CYTH4 that impacts gene expression in thyroid and has potential biological relevance for fibroids.

Supporting sustainability initiatives through biometeorology education and training - Michael J. Allen; Jennifer Vanos; David M. Hondula; Daniel J. Vecellio; David Knight; Hamed Mehdipoor; Rebekah Lucas; Chris Fuhrmann; Hanna Lokys; Angela Lees; Sheila Tavares Nascimento; Andrew C. W. Leung; et al. (International Journal of Biometeorology, 2017)

Controlled Ion Release from Novel Polyester/Ceramic Composites Enhances Osteoinductivity - Soheila Ali Akbari Ghavimi; Rama Rao Tata; Andrew J. Greenwald; Brittany N. Allen; David A. Grant; Sheila A. Grant; Mark W. Lee; Bret D. Ulery (The AAPS Journal, 2017)

Assessing mid-latitude dynamics in extreme event attribution systems - Daniel Mitchell; Paolo Davini; Ben Harvey; Neil Massey; Karsten Haustein; Tim Woollings; Richard Jones; Fredi Otto; Benoit Guillod; Sarah Sparrow; David Wallom; Myles Allen (Climate Dynamics, 2017)

A global database of nitrogen and phosphorus excretion rates of aquatic animals - Michael J. Vanni; Peter B. McIntyre; Dennis Allen; Diane L. Arnott; Jonathan P. Benstead; David J. Berg; Åge Brabrand; Sébastien Brosse; Paul A. Bukaveckas; Adriano Caliman; Krista A. Capps; Luciana S. Carneiro; et al. (Ecology, 2017)
Animals can be important in modulating ecosystem‐level nutrient cycling, although their importance varies greatly among species and ecosystems. Nutrient cycling rates of individual animals represent valuable data for testing the predictions of important frameworks such as the Metabolic Theory of Ecology ( MTE ) and ecological stoichiometry ( ES ). They also represent an important set of functional traits that may reflect both environmental and phylogenetic influences. Over the past two decades, studies of animal‐mediated nutrient cycling have increased dramatically, especially in aquatic ecosystems. Here we present a global compilation of aquatic animal nutrient excretion rates. The dataset includes 10,534 observations from freshwater and marine animals of N and/or P excretion rates. These observations represent 491 species, including most aquatic phyla. Coverage varies greatly among phyla and other taxonomic levels. The dataset includes information on animal body size, ambient temperature, taxonomic affiliations, and animal body N:P. This data set was used to test predictions of MTE and ES , as described in Vanni and McIntyre (2016; Ecology DOI : 10.1002/ecy.1582 ).

Seasonal spatial patterns of projected anthropogenic warming in complex terrain: a modeling study of the western US - David E. Rupp; Sihan Li; Philip W. Mote; Karen M. Shell; Neil Massey; Sarah N. Sparrow; David C. H. Wallom; Myles R. Allen (Climate Dynamics, 2017)

Global networks for invasion science: benefits, challenges and guidelines - Jasmin G. Packer; Laura A. Meyerson; David M. Richardson; Giuseppe Brundu; Warwick J. Allen; Ganesh P. Bhattarai; Hans Brix; Susan Canavan; Stefano Castiglione; Angela Cicatelli; Jan Čuda; James T. Cronin; et al. (Biological Invasions, 2017)

Biogeography of a plant invasion: drivers of latitudinal variation in enemy release - Warwick J. Allen; Laura A. Meyerson; David Cummings; John Anderson; Ganesh P. Bhattarai; James T. Cronin (Global Ecology and Biogeography, 2017)
Aim The relationship between herbivory and latitude may differ between native and invasive plant taxa, which can generate biogeographical heterogeneity in the strength of enemy release. Our aim was to compare latitudinal gradients in herbivory between native and invasive plants and investigate whether gradients are driven by local adaptation or phenotypic plasticity. Location North America. Methods Using sympatric native and invasive lineages of the wetland grass Phragmites australis and the specialist gall‐fly Lipara rufitarsis , we conducted a field survey to examine whether the relationship between herbivory (the proportion of stems galled) and latitude was parallel between lineages. In a subsequent common garden experiment, we assessed whether latitudinal gradients in herbivory were genetically based or driven by phenotypic plasticity. Results In the field, L. rufitarsis herbivory on the native P. australis lineage increased from 27% of stems galled in southern populations (36.5°) to 37% in northern populations (43.6°), whereas there was no relationship for the invasive lineage. Similar relationships were evident in the common garden experiment, indicating a genetic basis to latitudinal variation in herbivory. Moreover, the invasive lineage suffered five times less herbivory than the native lineage on average, supporting the enemy release hypothesis. However, a genetic basis to this pattern was absent in the common garden experiment, suggesting that local environmental conditions were responsible for the enemy release observed in nature. Specifically, stem height, diameter and density during the L. rufitarsis oviposition period appeared to be important drivers of herbivory. Main conclusions Non‐parallel gradients in herbivory may help explain the equivocal results of other studies that examine enemy release and biotic resistance at local scales, and can be an important mechanism promoting biogeographical variation in invasion success. We suggest that these latitudinal patterns in herbivory and other species interactions are likely to be a common phenomenon across a range of invaded systems.

Features of resilience - Elizabeth B. Connelly; Craig R. Allen; Kirk Hatfield; José M. Palma-Oliveira; David D. Woods; Igor Linkov (Environment Systems and Decisions, 2017)

Automated Gait Analysis Through Hues and Areas (AGATHA): A Method to Characterize the Spatiotemporal Pattern of Rat Gait - Heidi E. Kloefkorn; Travis R. Pettengill; Sara M. F. Turner; Kristi A. Streeter; Elisa J. Gonzalez-Rothi; David D. Fuller; Kyle D. Allen (Annals of Biomedical Engineering, 2017)

Recent declines in cancer incidence: related to the Great Recession? - Scarlett Lin Gomez; Alison J. Canchola; David O. Nelson; Theresa H. M. Keegan; Christina A. Clarke; Iona Cheng; Salma Shariff-Marco; Mindy DeRouen; Ralph Catalano; William A. Satariano; Kathleen Davidson-Allen; Sally L. Glaser (Cancer Causes & Control, 2017)

Evaluating the accuracy of self-report for the diagnosis of HIV-associated neurocognitive disorder (HAND): defining “symptomatic” versus “asymptomatic” HAND - Lisa C. Obermeit; Jessica Beltran; Kaitlin B. Casaletto; Donald R. Franklin; Scott Letendre; Ronald Ellis; Christine Fennema-Notestine; Florin Vaida; Ann C. Collier; Christina M. Marra; David Clifford; Benjamin Gelman; et al. (Journal of NeuroVirology, 2017)

Detecting spatial regimes in ecosystems - Shana M. Sundstrom; Tarsha Eason; R. John Nelson; David G. Angeler; Chris Barichievy; Ahjond S. Garmestani; Nicholas A.J. Graham; Dean Granholm; Lance Gunderson; Melinda Knutson; Kirsty L. Nash; Trisha Spanbauer; et al. (Ecology Letters, 2017)
Research on early warning indicators has generally focused on assessing temporal transitions with limited application of these methods to detecting spatial regimes. Traditional spatial boundary detection procedures that result in ecoregion maps are typically based on ecological potential (i.e. potential vegetation), and often fail to account for ongoing changes due to stressors such as land use change and climate change and their effects on plant and animal communities. We use Fisher information, an information theory‐based method, on both terrestrial and aquatic animal data (U.S. Breeding Bird Survey and marine zooplankton) to identify ecological boundaries, and compare our results to traditional early warning indicators, conventional ecoregion maps and multivariate analyses such as nMDS and cluster analysis. We successfully detected spatial regimes and transitions in both terrestrial and aquatic systems using Fisher information. Furthermore, Fisher information provided explicit spatial information about community change that is absent from other multivariate approaches. Our results suggest that defining spatial regimes based on animal communities may better reflect ecological reality than do traditional ecoregion maps, especially in our current era of rapid and unpredictable ecological change.

Apolipoprotein E ε4 genotype status is not associated with neuroimaging outcomes in a large cohort of HIV+ individuals - Sarah A. Cooley; Robert H. Paul; Christine Fennema-Notestine; Erin E. Morgan; Florin Vaida; Qianqian Deng; Jie Ashley Chen; Scott Letendre; Ronald Ellis; David B. Clifford; Christina M. Marra; Ann C. Collier; et al. (Journal of NeuroVirology, 2016)

Panarchy use in environmental science for risk and resilience planning - David G. Angeler; Craig R. Allen; Ahjond S. Garmestani; Lance H. Gunderson; Igor Linkov (Environment Systems and Decisions, 2016)

Plant hydraulic responses to long-term dry season nitrogen deposition alter drought tolerance in a Mediterranean-type ecosystem - Alexandria L. Pivovaroff; Louis S. Santiago; George L. Vourlitis; David A. Grantz; Michael F. Allen (Oecologia, 2016)

Expert consensus on an in vitro approach to assess pulmonary fibrogenic potential of aerosolized nanomaterials - Amy J. Clippinger; Arti Ahluwalia; David Allen; James C. Bonner; Warren Casey; Vincent Castranova; Raymond M. David; Sabina Halappanavar; Jon A. Hotchkiss; Annie M. Jarabek; Monika Maier; William Polk; et al. (Archives of Toxicology, 2016)

The impacts of increasing drought on forest dynamics, structure, and biodiversity in the United States - James S. Clark; Louis Iverson; Christopher W. Woodall; Craig D. Allen; David M. Bell; Don C. Bragg; Anthony W. D'Amato; Frank W. Davis; Michelle H. Hersh; Ines Ibanez; Stephen T. Jackson; Stephen Matthews; et al. (Global Change Biology, 2016)
We synthesize insights from current understanding of drought impacts at stand‐to‐biogeographic scales, including management options, and we identify challenges to be addressed with new research. Large stand‐level shifts underway in western forests already are showing the importance of interactions involving drought, insects, and fire. Diebacks, changes in composition and structure, and shifting range limits are widely observed. In the eastern US , the effects of increasing drought are becoming better understood at the level of individual trees, but this knowledge cannot yet be confidently translated to predictions of changing structure and diversity of forest stands. While eastern forests have not experienced the types of changes seen in western forests in recent decades, they too are vulnerable to drought and could experience significant changes with increased severity, frequency, or duration in drought. Throughout the continental United States, the combination of projected large climate‐induced shifts in suitable habitat from modeling studies and limited potential for the rapid migration of tree populations suggests that changing tree and forest biogeography could substantially lag habitat shifts already underway. Forest management practices can partially ameliorate drought impacts through reductions in stand density, selection of drought‐tolerant species and genotypes, artificial regeneration, and the development of multistructured stands. However, silvicultural treatments also could exacerbate drought impacts unless implemented with careful attention to site and stand characteristics. Gaps in our understanding should motivate new research on the effects of interactions involving climate and other species at the stand scale and how interactions and multiple responses are represented in models. This assessment indicates that, without a stronger empirical basis for drought impacts at the stand scale, more complex models may provide limited guidance.

Magnetic Capture of a Molecular Biomarker from Synovial Fluid in a Rat Model of Knee Osteoarthritis - Elena G. Yarmola; Yash Shah; David P. Arnold; Jon Dobson; Kyle D. Allen (Annals of Biomedical Engineering, 2016)

Advancing Product Quality: a Summary of the Second FDA/PQRI Conference - Lawrence X. Yu; Ilgaz Akseli; Barbara Allen; Gregory Amidon; Tara Gooen Bizjak; Ashley Boam; Margaret Caulk; David Doleski; Joseph Famulare; Adam C. Fisher; Scott Furness; Brian Hasselbalch; et al. (The AAPS Journal, 2016)

Temporal variability in aboveground plant biomass decreases as spatial variability increases - Devan Allen McGranahan; Torre J. Hovick; R. Dwayne Elmore; David M. Engle; Samuel D. Fuhlendorf; Stephen L. Winter; James R. Miller; Diane M. Debinski (Ecology, 2016)
Ecological theory predicts that diversity decreases variability in ecosystem function. We predict that, at the landscape scale, spatial variability created by a mosaic of contrasting patches that differ in time since disturbance will decrease temporal variability in aboveground plant biomass. Using data from a multi‐year study of seven grazed tallgrass prairie landscapes, each experimentally managed for one to eight patches, we show that increased spatial variability driven by spatially patchy fire and herbivory reduces temporal variability in aboveground plant biomass. This pattern is associated with statistical evidence for the portfolio effect and a positive relationship between temporal variability and functional group synchrony as predicted by metacommunity variability theory. As disturbance from fire and grazing interact to create a shifting mosaic of spatially heterogeneous patches within a landscape, temporal variability in aboveground plant biomass can be dampened. These results suggest that spatially heterogeneous disturbance regimes contribute to a portfolio of ecosystem functions provided by biodiversity, including wildlife habitat, fuel, and forage. We discuss how spatial patterns of disturbance drive variability within and among patches.

Colorectal polyp prevention by daily aspirin use is abrogated among active smokers - David A. Drew; Gyuhyeong Goh; Allen Mo; James J. Grady; Faripour Forouhar; Gretchen Egan; Helen Swede; Daniel W. Rosenberg; Richard G. Stevens; Thomas J. Devers (Cancer Causes & Control, 2016)

Climate change, climate justice and the application of probabilistic event attribution to summer heat extremes in the California Central Valley - Roberto Mera; Neil Massey; David E. Rupp; Philip Mote; Myles Allen; Peter C. Frumhoff (Climatic Change, 2015)

Best practice BioBanking of human heart tissue - Sean Lal; Amy Li; David Allen; Paul D. Allen; Paul Bannon; Tim Cartmill; Roger Cooke; Alan Farnsworth; Anne Keogh; Cristobal dos Remedios (Biophysical Reviews, 2015)

Validation of Xanthophyll Levels in Catfish Fillets Using Digital Photography - Bochao Hu; David Cline; Allen Davis; Yifen Wang; Shaoyang Liu (Journal of Aquatic Food Product Technology, 2015)

CSF biomarkers of monocyte activation and chemotaxis correlate with magnetic resonance spectroscopy metabolites during chronic HIV disease - Albert M. Anderson; Christine Fennema-Notestine; Anya Umlauf; Michael J. Taylor; David B. Clifford; Christina M. Marra; Ann C. Collier; Benjamin B. Gelman; Justin C. McArthur; J. Allen McCutchan; David M. Simpson; Susan Morgello; et al. (Journal of NeuroVirology, 2015)

Adaptive invasive species distribution models: a framework for modeling incipient invasions - Daniel R. Uden; Craig R. Allen; David G. Angeler; Lucía Corral; Kent A. Fricke (Biological Invasions, 2015)

Equipped to deal with uncertainty in climate and impacts predictions: lessons from internal peer review - Anna Wesselink; Andrew Juan Challinor; James Watson; Keith Beven; Icarus Allen; Helen Hanlon; Ana Lopez; Susanne Lorenz; Friederike Otto; Andy Morse; Cameron Rye; Stephane Saux-Picard; et al. (Climatic Change, 2015)

Membrane Protein Structure, Function, and Dynamics: a Perspective from Experiments and Theory - Zoe Cournia; Toby W. Allen; Ioan Andricioaei; Bruno Antonny; Daniel Baum; Grace Brannigan; Nicolae-Viorel Buchete; Jason T. Deckman; Lucie Delemotte; Coral del Val; Ran Friedman; Paraskevi Gkeka; et al. (The Journal of Membrane Biology, 2015)

Spatial Patterns and Functional Redundancies in a Changing Boreal Lake Landscape - David G. Angeler; Craig R. Allen; Daniel R. Uden; Richard K. Johnson (Ecosystems, 2015)

Linking degradation status with ecosystem vulnerability to environmental change - David G. Angeler; Didier L. Baho; Craig R. Allen; Richard K. Johnson (Oecologia, 2015)

Extraordinary diversity of reef corals in the South China Sea - Danwei Huang; Wilfredo Y. Licuanan; Bert W. Hoeksema; Chaolun Allen Chen; Put O. Ang; Hui Huang; David J. W. Lane; Si Tuan Vo; Zarinah Waheed; Yang Amri Affendi; Thamasak Yeemin; Loke Ming Chou (Marine Biodiversity, 2015)

Managing lateral infiltration on wide beds in clay and sandy clay loam using Hydrus 2D - Ghani Akbar; Steven Raine; Allen David McHugh; Greg Hamilton (Irrigation Science, 2015)

BioEarth: Envisioning and developing a new regional earth system model to inform natural and agricultural resource management - Jennifer C. Adam; Jennie C. Stephens; Serena H. Chung; Michael P. Brady; R. David Evans; Chad E. Kruger; Brian K. Lamb; Mingliang Liu; Claudio O. Stöckle; Joseph K. Vaughan; Kirti Rajagopalan; John A. Harrison; et al. (Climatic Change, 2015)

Community control on growth and survival of an exotic shrub - Zachary T. Brym; David Allen; Inés Ibáñez (Biological Invasions, 2014)

Assessing and managing freshwater ecosystems vulnerable to environmental change - David G. Angeler; Craig R. Allen; Hannah E. Birgé; Stina Drakare; Brendan G. McKie; Richard K. Johnson (Ambio, 2014)

Unsupported inferences of high‐severity fire in historical dry forests of the western U nited S tates: response to W illiams and B aker - Peter Z. Fulé; Thomas W. Swetnam; Peter M. Brown; Donald A. Falk; David L. Peterson; Craig D. Allen; Gregory H. Aplet; Mike A. Battaglia; Dan Binkley; Calvin Farris; Robert E. Keane; Ellis Q. Margolis; et al. (Global Ecology and Biogeography, 2014)
Reconstructions of dry western US forests in the late 19th century in A rizona, C olorado and O regon based on G eneral L and O ffice records were used by W illiams & B aker (2012; G lobal E cology and B iogeography , 21 , 1042–1052; hereafter W & B ) to infer past fire regimes with substantial moderate and high‐severity burning. The authors concluded that present‐day large, high‐severity fires are not distinguishable from historical patterns. We present evidence of important errors in their study. First, the use of tree size distributions to reconstruct past fire severity and extent is not supported by empirical age–size relationships nor by studies that directly quantified disturbance history in these forests. Second, the fire severity classification of W & B is qualitatively different from most modern classification schemes, and is based on different types of data, leading to an inappropriate comparison. Third, we note that while W & B asserted ‘surprising’ heterogeneity in their reconstructions of stand density and species composition, their data are not substantially different from many previous studies which reached very different conclusions about subsequent forest and fire behaviour changes. Contrary to the conclusions of W & B , the preponderance of scientific evidence indicates that conservation of dry forest ecosystems in the western U nited S tates and their ecological, social and economic value is not consistent with a present‐day disturbance regime of large, high‐severity fires, especially under changing climate.

Panarchy: Theory and Application - Craig R. Allen; David G. Angeler; Ahjond S. Garmestani; Lance H. Gunderson; C. S. Holling (Ecosystems, 2014)

HIV-associated distal neuropathic pain is associated with smaller total cerebral cortical gray matter - John R. Keltner; Christine Fennema-Notestine; Florin Vaida; Dongzhe Wang; Donald R. Franklin; Robert H. Dworkin; Chelsea Sanders; J. Allen McCutchan; Sarah L. Archibald; David J. Miller; George Kesidis; Clint Cushman; et al. (Journal of NeuroVirology, 2014)

Remote Antarctic feeding ground important for east Australian humpback whales - Rochelle Constantine; Debbie Steel; Judy Allen; Megan Anderson; Olive Andrews; C. Scott Baker; Peta Beeman; Daniel Burns; Jean-Benoît Charrassin; Simon Childerhouse; Michael Double; Paul Ensor; et al. (Marine Biology, 2014)

Discontinuities, cross‐scale patterns, and the organization of ecosystems - Kirsty L. Nash; Craig R. Allen; David G. Angeler; Chris Barichievy; Tarsha Eason; Ahjond S. Garmestani; Nicholas A. J. Graham; Dean Granholm; Melinda Knutson; R. John Nelson; Magnus Nyström; Craig A. Stow; et al. (Ecology, 2014)
Ecological structures and processes occur at specific spatiotemporal scales, and interactions that occur across multiple scales mediate scale‐specific (e.g., individual, community, local, or regional) responses to disturbance. Despite the importance of scale, explicitly incorporating a multi‐scale perspective into research and management actions remains a challenge. The discontinuity hypothesis provides a fertile avenue for addressing this problem by linking measureable proxies to inherent scales of structure within ecosystems. Here we outline the conceptual framework underlying discontinuities and review the evidence supporting the discontinuity hypothesis in ecological systems. Next we explore the utility of this approach for understanding cross‐scale patterns and the organization of ecosystems by describing recent advances for examining nonlinear responses to disturbance and phenomena such as extinctions, invasions, and resilience. To stimulate new research, we present methods for performing discontinuity analysis, detail outstanding knowledge gaps, and discuss potential approaches for addressing these gaps.

Temporal, spatial, and body size effects on growth rates of loggerhead sea turtles (Caretta caretta) in the Northwest Atlantic - Karen A. Bjorndal; Barbara A. Schroeder; Allen M. Foley; Blair E. Witherington; Michael Bresette; David Clark; Richard M. Herren; Michael D. Arendt; Jeffrey R. Schmid; Anne B. Meylan; Peter A. Meylan; Jane A. Provancha; et al. (Marine Biology, 2013)

Increases in brain white matter abnormalities and subcortical gray matter are linked to CD4 recovery in HIV infection - Christine Fennema-Notestine; Ronald J. Ellis; Sarah L. Archibald; Terry L. Jernigan; Scott L. Letendre; Randy J. Notestine; Michael J. Taylor; Rebecca J. Theilmann; Michelle D. Julaton; David J. Croteau; Tanya Wolfson; Robert K. Heaton; et al. (Journal of NeuroVirology, 2013)

Erratum to: Adaptive feedback analysis and control of programmable stimuli for assessment of cerebrovascular function - Lingke Fan; Glen Bush; Emmanuel Katsogridakis; David M. Simpson; Robert Allen; John Potter; Anthony A. Birch; Ronney B. Panerai (Medical & Biological Engineering & Computing, 2013)

Streptolysin-O/antibiotics adjunct therapy modulates site-specific expression of extracellular matrix and inflammatory genes in lungs of Rhodococcus equi infected foals - Volkan Gurel; Kristyn Lambert; Allen E. Page; Alan T. Loynachan; Katherine Huges; John F. Timoney; Michael Fettinger; David W. Horohov; John McMichael (Veterinary Research Communications, 2013)

Adaptive feedback analysis and control of programmable stimuli for assessment of cerebrovascular function - Lingke Fan; Glen Bush; Emmanuel Katsogridakis; David M. Simpson; Robert Allen; John Potter; Anthony A. Birch; Ronney B. Panerai (Medical & Biological Engineering & Computing, 2013)

Predicting ecosystem stability from community composition and biodiversity - Claire de Mazancourt; Forest Isbell; Allen Larocque; Frank Berendse; Enrica De Luca; James B. Grace; Bart Haegeman; H. Wayne Polley; Christiane Roscher; Bernhard Schmid; David Tilman; Jasper van Ruijven; et al. (Ecology Letters, 2013)
As biodiversity is declining at an unprecedented rate, an important current scientific challenge is to understand and predict the consequences of biodiversity loss. Here, we develop a theory that predicts the temporal variability of community biomass from the properties of individual component species in monoculture. Our theory shows that biodiversity stabilises ecosystems through three main mechanisms: (1) asynchrony in species’ responses to environmental fluctuations, (2) reduced demographic stochasticity due to overyielding in species mixtures and (3) reduced observation error (including spatial and sampling variability). Parameterised with empirical data from four long‐term grassland biodiversity experiments, our prediction explained 22–75% of the observed variability, and captured much of the effect of species richness. Richness stabilised communities mainly by increasing community biomass and reducing the strength of demographic stochasticity. Our approach calls for a re‐evaluation of the mechanisms explaining the effects of biodiversity on ecosystem stability.

A review of the abuse potential assessment of atomoxetine: a nonstimulant medication for attention-deficit/hyperactivity disorder - Himanshu P. Upadhyaya; Durisala Desaiah; Kory J. Schuh; Frank P. Bymaster; Mary J. Kallman; David O. Clarke; Todd M. Durell; Paula T. Trzepacz; David O. Calligaro; Eric S. Nisenbaum; Paul J. Emmerson; Leslie M. Schuh; et al. (Psychopharmacology, 2013)

A Review of Emergency Cardiopulmonary Bypass for Severe Poisoning by Cardiotoxic Drugs - Nicholas J. Johnson; David F. Gaieski; Steven R. Allen; Jeanmarie Perrone; Francis DeRoos (Journal of Medical Toxicology, 2013)

A system identification analysis of neural adaptation dynamics and nonlinear responses in the local reflex control of locust hind limbs - Oliver P. Dewhirst; Natalia Angarita-Jaimes; David M. Simpson; Robert Allen; Philip L. Newland (Journal of Computational Neuroscience, 2013)

An Invasive Grass Increases Live Fuel Proportion and Reduces Fire Spread in a Simulated Grassland - Devan Allen McGranahan; David M. Engle; James R. Miller; Diane M. Debinski (Ecosystems, 2013)

Diabetes and risk of pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium - Joanne W. Elena; Emily Steplowski; Kai Yu; Patricia Hartge; Geoffrey S. Tobias; Michelle J. Brotzman; Stephen J. Chanock; Rachael Z. Stolzenberg-Solomon; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Kathy Helzlsouer; Eric J. Jacobs; et al. (Cancer Causes & Control, 2013)

CD4+ Regulatory and Effector/Memory T Cell Subsets Profile Motor Dysfunction in Parkinson’s Disease - Jessica A. Hutter Saunders; Katherine A. Estes; Lisa M. Kosloski; Heather E. Allen; Kathryn M. Dempsey; Diego R. Torres-Russotto; Jane L. Meza; Pamela M. Santamaria; John M. Bertoni; Daniel L. Murman; Hesham H. Ali; David G. Standaert; et al. (Journal of Neuroimmune Pharmacology, 2012)
Animal models and clinical studies have linked the innate and adaptive immune system to the pathology of Parkinson’s disease (PD). Despite such progress, the specific immune responses that influence disease progression have eluded investigators. Herein, we assessed relationships between T cell phenotype and function with PD progression. Peripheral blood lymphocytes from two separate cohorts, a discovery cohort and a validation cohort, totaling 113 PD patients and 96 age- and environment-matched caregivers were examined by flow cytometric analysis and T cell proliferation assays. Increased effector/memory T cells (Tem), defined as CD45RO+ and FAS+ CD4+ T cells and decreased CD31+ and α4β7+ CD4+ T cells were associated with progressive Unified Parkinson’s Disease Rating Scale III scores. However, no associations were seen between immune biomarkers and increased age or disease duration. Impaired abilities of regulatory T cells (Treg) from PD patients to suppress effector T cell function was observed. These data support the concept that chronic immune stimulation, notably Tem activation and Treg dysfunction is linked to PD pathobiology and disease severity, but not disease duration. The association of T cell phenotypes with motor symptoms provides fresh avenues for novel biomarkers and therapeutic designs.

Mitochondrial DNA variation and HIV-associated sensory neuropathy in CHARTER - Emily R. Holzinger; Todd Hulgan; Ronald J. Ellis; David C. Samuels; Marylyn D. Ritchie; David W. Haas; Asha R. Kallianpur; Cinnamon S. Bloss; David B. Clifford; Ann C. Collier; Benjamin B. Gelman; Christina M. Marra; et al. (Journal of NeuroVirology, 2012)

Use of an Airborne Lidar System to Model Plant Species Composition and Diversity of Mediterranean Oak Forests - WILLIAM D. SIMONSON; HARRIET D. ALLEN; DAVID A. COOMES (Conservation Biology, 2012)
Airborne lidar is a remote‐sensing tool of increasing importance in ecological and conservation research due to its ability to characterize three‐dimensional vegetation structure. If different aspects of plant species diversity and composition can be related to vegetation structure, landscape‐level assessments of plant communities may be possible. We examined this possibility for Mediterranean oak forests in southern Portugal, which are rich in biological diversity but also threatened. We compared data from a discrete, first‐and‐last return lidar data set collected for 31 plots of cork oak (Quercus suber) and Algerian oak (Quercus canariensis) forest with field data to test whether lidar can be used to predict the vertical structure of vegetation, diversity of plant species, and community type. Lidar‐ and field‐measured structural data were significantly correlated (up to r= 0.85). Diversity of forest species was significantly associated with lidar‐measured vegetation height (R 2 = 0.50, p

Intensity attenuation for active crustal regions - Trevor I. Allen; David J. Wald; C. Bruce Worden (Journal of Seismology, 2012)

On the long-term context of the 1997–2009 ‘Big Dry’ in South-Eastern Australia: insights from a 206-year multi-proxy rainfall reconstruction - Joëlle Gergis; Ailie Jane Eyre Gallant; Karl Braganza; David John Karoly; Kathryn Allen; Louise Cullen; Rosanne D’Arrigo; Ian Goodwin; Pauline Grierson; Shayne McGregor (Climatic Change, 2012)

Genetic features of cerebrospinal fluid-derived subtype B HIV-1 tat - Jun Yong Choi; George K. Hightower; Joseph K. Wong; Robert Heaton; Steven Woods; Igor Grant; Thomas D. Marcotte; Ronald J. Ellis; Scott L. Letendre; Ann C. Collier; Christina M. Marra; David B. Clifford; et al. (Journal of NeuroVirology, 2012)

Temporal turnover in the composition of tropical tree communities: functional determinism and phylogenetic stochasticity - Nathan G. Swenson; James C. Stegen; Stuart J. Davies; David L. Erickson; Jimena Forero-Montaña; Allen H. Hurlbert; W. John Kress; Jill Thompson; María Uriarte; S. Joseph Wright; Jess K. Zimmerman (Ecology, 2012)
The degree to which turnover in biological communities is structured by deterministic or stochastic factors and the identities of influential deterministic factors are fundamental, yet unresolved, questions in ecology. Answers to these questions are particularly important for projecting the fate of forests with diverse disturbance histories worldwide. To uncover the processes governing turnover we use species‐level molecular phylogenies and functional trait data sets for two long‐term tropical forest plots with contrasting disturbance histories: one forest is older‐growth, and one was recently disturbed. Having both phylogenetic and functional information further allows us to parse out the deterministic influences of different ecological filters. With the use of null models we find that compositional turnover was random with respect to phylogeny on average, but highly nonrandom with respect to measured functional traits. Furthermore, as predicted by a deterministic assembly process, the older‐growth and disturbed forests were characterized by less than and greater than expected functional turnover, respectively. These results suggest that the abiotic environment, which changes due to succession in the disturbed forest, strongly governs the temporal dynamics of disturbed and undisturbed tropical forests. Predicting future changes in the composition of disturbed and undisturbed forests may therefore be tractable when using a functional‐trait‐based approach.

Effects of biotic disturbances on forest carbon cycling in the U nited S tates and C anada - Jeffrey A. Hicke; Craig D. Allen; Ankur R. Desai; Michael C. Dietze; Ronald J. Hall; Edward H. (Ted) Hogg; Daniel M. Kashian; David Moore; Kenneth F. Raffa; Rona N. Sturrock; James Vogelmann (Global Change Biology, 2012)
Forest insects and pathogens are major disturbance agents that have affected millions of hectares in N orth A merica in recent decades, implying significant impacts to the carbon ( C ) cycle. Here, we review and synthesize published studies of the effects of biotic disturbances on forest C cycling in the U nited S tates and C anada. Primary productivity in stands was reduced, sometimes considerably, immediately following insect or pathogen attack. After repeated growth reductions caused by some insects or pathogens or a single infestation by some bark beetle species, tree mortality occurred, altering productivity and decomposition. In the years following disturbance, primary productivity in some cases increased rapidly as a result of enhanced growth by surviving vegetation, and in other cases increased slowly because of lower forest regrowth. In the decades following tree mortality, decomposition increased as a result of the large amount of dead organic matter. Net ecosystem productivity decreased immediately following attack, with some studies reporting a switch to a C source to the atmosphere, and increased afterward as the forest regrew and dead organic matter decomposed. Large variability in C cycle responses arose from several factors, including type of insect or pathogen, time since disturbance, number of trees affected, and capacity of remaining vegetation to increase growth rates following outbreak. We identified significant knowledge gaps, including limited understanding of carbon cycle impacts among different biotic disturbance types (particularly pathogens), their impacts at landscape and regional scales, and limited capacity to predict disturbance events and their consequences for carbon cycling. We conclude that biotic disturbances can have major impacts on forest C stocks and fluxes and can be large enough to affect regional C cycling. However, additional research is needed to reduce the uncertainties associated with quantifying biotic disturbance effects on the N orth A merican C budget.

The Business of Forest Enterprise / Urban Ecosystems / Forest Policy / Biosecurity - David Nicholls; Allen Brackley; Charles Keegan; Colin Sorenson; Jean Daniels; Erik Berg; Charles Gale; Robert Campbell; Charles Gale; Charles Keegan; Erik Berg; Colin Sorenson; et al. (Journal of Forestry, 2011)
172Business clusters are geographic concentrations of companies that provide mutual advantages for their participants. Clusters can include diverse members including competitors, customers, partners, and/or suppliers. In Alaska, wood products business clusters can have unique challenges associated with remote locations, high raw material costs, limited local markets, and potentially long transportation distances. Further, multiple land ownership near communities (for example state versus federal ownership) can influence raw material procurement, since different administrative processes for timber harvesting may be required. This study evaluates 2 resource dependent communities in southeast Alaska (Haines, AK and Craig, AK), seeking to identify elements that could enhance their potential for wood products clusters and new business formation. We consider how the flow of forest resources, from harvest to finished product, can influence local communities and either enhance or limit opportunities for wood products businesses. We evaluate the effect of various product mixes—including firewood, woody residues, house logs, lumber, and secondary wood products—on the composition, scale, and dynamics of wood products firms. We consider the effect of harvesting practices and proximity to timber sales in evaluating how land ownership can influence the viability of wood products clusters. Lastly we consider the impact of transportation costs on serving local and export markets. Our research builds upon past work in Alaska that evaluated national-forest based communities in Alaska, finding opportunities for greater innovation, higher productivity, and greater social well-being associated with wood products clusters.

Life history and habitat use of the speckled worm eel, Myrophis punctatus, along the east coast of the United States - Kenneth W. Able; Dennis M. Allen; Gretchen Bath-Martin; Jonathan A. Hare; Donald E. Hoss; Katrin E. Marancik; Perce M. Powles; David E. Richardson; J. Christopher Taylor; Harvey J. Walsh; Stanley M. Warlen; Charles Wenner (Environmental Biology of Fishes, 2011)

Plasma matrix metalloproteinase-9 response to eccentric exercise of the elbow flexors - Molly C. Madden; William C. Byrnes; Jacob A. Lebin; Matthew E. Batliner; David L. Allen (European Journal of Applied Physiology, 2011)

Seabed foraging by Antarctic krill: Implications for stock assessment, bentho‐pelagic coupling, and the vertical transfer of iron - Katrin Schmidt; Angus Atkinson; Sebastian Steigenberger; Sophie Fielding; Margaret C. M. Lindsay; David W. Pond; Geraint A. Tarling; Thor A. Klevjer; Claire S. Allen; Stephen Nicol; Eric P. Achterberg (Limnology and Oceanography, 2011)
A compilation of more than 30 studies shows that adult Antarctic krill ( Euphausia superba ) may frequent benthic habitats year‐round, in shelf as well as oceanic waters and throughout their circumpolar range. Net and acoustic data from the Scotia Sea show that in summer 2‐20% of the population reside at depths between 200 and 2000 m, and that large aggregations can form above the seabed. Local differences in the vertical distribution of krill indicate that reduced feeding success in surface waters, either due to predator encounter or food shortage, might initiate such deep migrations and results in benthic feeding. Fatty acid and microscopic analyses of stomach content confirm two different foraging habitats for Antarctic krill: the upper ocean, where fresh phytoplankton is the main food source, and deeper water or the seabed, where detritus and copepods are consumed. Krill caught in upper waters retain signals of benthic feeding, suggesting frequent and dynamic exchange between surface and seabed. Krill contained up to 260 nmol iron per stomach when returning from seabed feeding. About 5% of this iron is labile, i.e., potentially available to phytoplankton. Due to their large biomass, frequent benthic feeding, and acidic digestion of particulate iron, krill might facilitate an input of new iron to Southern Ocean surface waters. Deep migrations and foraging at the seabed are significant parts of krill ecology, and the vertical fluxes involved in this behavior are important for the coupling of benthic and pelagic food webs and their elemental repositories.

Clinical factors related to brain structure in HIV: the CHARTER study - Terry L. Jernigan; Sarah L. Archibald; Christine Fennema-Notestine; Michael J. Taylor; Rebecca J. Theilmann; Michelle D. Julaton; Randy J. Notestine; Tanya Wolfson; Scott L. Letendre; Ronald J. Ellis; Robert K. Heaton; Anthony C. Gamst; et al. (Journal of NeuroVirology, 2011)

Millennial precipitation reconstruction for the Jemez Mountains, New Mexico, reveals changingb drought signal - Ramzi Touchan; Connie A. Woodhouse; David M. Meko; Craig Allen (International Journal of Climatology, 2011)
Drought is a recurring phenomenon in the American Southwest. Since the frequency and severity of hydrologic droughts and other hydroclimatic events are of critical importance to the ecology and rapidly growing human population of this region, knowledge of long‐term natural hydroclimatic variability is valuable for resource managers and policy‐makers. An October–June precipitation reconstruction for the period AD 824–2007 was developed from multi‐century tree‐ring records of Pseudotsuga menziesii (Douglas‐fir), Pinus strobiformis (Southwestern white pine) and Pinus ponderosa (Ponderosa pine) for the Jemez Mountains in Northern New Mexico. Calibration and verification statistics for the period 1896–2007 show a high level of skill, and account for a significant portion of the observed variance (>50%) irrespective of which period is used to develop or verify the regression model. Split‐sample validation supports our use of a reconstruction model based on the full period of reliable observational data (1896–2007). A recent segment of the reconstruction (2000–2006) emerges as the driest 7‐year period sensed by the trees in the entire record. That this period was only moderately dry in precipitation anomaly likely indicates accentuated stress from other factors, such as warmer temperatures. Correlation field maps of actual and reconstructed October–June total precipitation, sea surface temperatures and 500‐mb geopotential heights show characteristics that are similar to those indicative of El Niño–Southern Oscillation patterns, particularly with regard to ocean and atmospheric conditions in the equatorial and north Pacific. Our 1184‐year reconstruction of hydroclimatic variability provides long‐term perspective on current and 20th century wet and dry events in Northern New Mexico, is useful to guide expectations of future variability, aids sustainable water management, provides scenarios for drought planning and as inputs for hydrologic models under a broader range of conditions than those provided by historical climate records. Copyright © 2010 Royal Meteorological Society

A molecular phylogenetic analysis of Bulinus (Gastropoda: Planorbidae) with conserved nuclear genes - Aslak Jørgensen; Henry Madsen; Allen Nalugwa; Silvester Nyakaana; David Rollinson; J. Russell Stothard; Thomas K. Kristensen (Zoologica Scripta, 2011)
Jørgensen, A., Madsen, H., Nalugwa, A., Nyakaana, S., Rollinson, D., Stothard, J. R. & Kristensen, T. K. A molecular phylogenetic analysis of Bulinus (Gastropoda: Planorbidae) with conserved nuclear genes. — Zoologica Scripta , 40 , 126–136. Mutational saturation of inspected DNA loci and topological incongruence in the phylogenetic inferences have previously confounded attempts to resolve the evolutionary relationships within the freshwater snail genus Bulinus . Traditionally, the 37 species of Bulinus are placed within the four species groups and the evolutionary divergence between groups is substantial. With an intention to shed new light on species group relationships, the present study was designed to investigate the basal divergences in the phylogeny of Bulinus using highly conserved nuclear genes. The resolved phylogeny inferred that the four species groups of Bulinus were monophyletic and Shimodaira‐Hasegawa topology tests found them to be significantly supported. The Bulinus truncatus/tropicus species complex and Bulinus wrighti ( Bulinus reticulatus group) formed a well‐supported sister‐group relationship. The Bulinus africanus species group was the sister‐group to the clade ( Bulinus truncatus/tropicus + B. wrighti ) with the Bulinus forskalii species group as the sister‐group to these taxa. The sister‐group relationship between Indoplanorbis and Bulinus was non‐significant and the basal clade support of Bulinus improved upon exclusion of Indoplanorbis . The finding of basal long branches of Bulinus species originating from Madagascar strongly suggests the presence of additional cryptic species and an evolutionary scenario influenced by this island’s geological vicariance from the African mainland. Speciation by polyploidy was inferred to have evolved within a clade in the Bulinus truncatus/tropicus species complex. Although the monophyletic status of each species group was firmly supported, it was difficult to establish species group concepts equally across the variations and place this precisely in a specific temporal framework.

HIV-associated neurocognitive disorders before and during the era of combination antiretroviral therapy: differences in rates, nature, and predictors - Robert K. Heaton; Donald R. Franklin; Ronald J. Ellis; J. Allen McCutchan; Scott L. Letendre; Shannon LeBlanc; Stephanie H. Corkran; Nichole A. Duarte; David B. Clifford; Steven P. Woods; Ann C. Collier; Christina M. Marra; et al. (Journal of NeuroVirology, 2011)

Microsatellite loci for testing temporal changes in the population genetics of the Florida mouse (Podomys floridanus) - Catalina Rivadeneira; Julie M. Allen; David L. Reed (Conservation Genetics Resources, 2011)

Dormancy and Flowering Are Regulated by the Reciprocal Interaction Between Cytokinin and Gibberellin in Zantedeschia - Arvind Kumar Subbaraj; Keith Allen Funnell; David John Woolley (Journal of Plant Growth Regulation, 2010)

Habitat and conservation of the enigmatic damselfly Ischnura pumilio - Katherine A. Allen; Mike G. Le Duc; David J. Thompson (Journal of Insect Conservation, 2010)

Deletion of the eIFiso4G subunit of the Arabidopsis eIFiso4F translation initiation complex impairs health and viability - Andrew D. Lellis; M. Leah Allen; Alice W. Aertker; Jonathan K. Tran; David M. Hillis; Courtney R. Harbin; Christian Caldwell; Daniel R. Gallie; Karen S. Browning (Plant Molecular Biology, 2010)

What limits exercise during high-intensity aerobic exercise? - David Allen; Håkan Westerblad (European Journal of Applied Physiology, 2010)

Niche conservatism as an emerging principle in ecology and conservation biology - John J. Wiens; David D. Ackerly; Andrew P. Allen; Brian L. Anacker; Lauren B. Buckley; Howard V. Cornell; Ellen I. Damschen; T. Jonathan Davies; John‐Arvid Grytnes; Susan P. Harrison; Bradford A. Hawkins; Robert D. Holt; et al. (Ecology Letters, 2010)
The diversity of life is ultimately generated by evolution, and much attention has focused on the rapid evolution of ecological traits. Yet, the tendency for many ecological traits to instead remain similar over time [niche conservatism (NC)] has many consequences for the fundamental patterns and processes studied in ecology and conservation biology. Here, we describe the mounting evidence for the importance of NC to major topics in ecology (e.g. species richness, ecosystem function) and conservation (e.g. climate change, invasive species). We also review other areas where it may be important but has generally been overlooked, in both ecology (e.g. food webs, disease ecology, mutualistic interactions) and conservation (e.g. habitat modification). We summarize methods for testing for NC, and suggest that a commonly used and advocated method (involving a test for phylogenetic signal) is potentially problematic, and describe alternative approaches. We suggest that considering NC: (1) focuses attention on the within‐species processes that cause traits to be conserved over time, (2) emphasizes connections between questions and research areas that are not obviously related (e.g. invasives, global warming, tropical richness), and (3) suggests new areas for research (e.g. why are some clades largely nocturnal? why do related species share diseases?).

Variability of United States Isolates of Macrophomina phaseolina Based on Simple Sequence Repeats and Cross Genus Transferability to Related Genera Within Botryosphaeriaceae - Richard E. Baird; Phillip A. Wadl; Thomas Allen; David McNeill; Xinwang Wang; John K. Moulton; Timothy A. Rinehart; Hamed K. Abbas; Thomas Shier; Robert N. Trigiano (Mycopathologia, 2010)

Erratum to: Interaction between groundwater, the hyporheic zone and a Chalk stream: a case study from the River Lambourn, UK - David J. Allen; W. George Darling; Daren C. Gooddy; Daniel J. Lapworth; Andrew J. Newell; Ann T. Williams; Debbie Allen; Corinna Abesser (Hydrogeology Journal, 2010)

Interaction between groundwater, the hyporheic zone and a Chalk stream: a case study from the River Lambourn, UK - David J. Allen; W. George Darling; Daren C. Gooddy; Daniel J. Lapworth; Andrew J. Newell; Ann T. Williams; Debbie Allen; Corinna Abesser (Hydrogeology Journal, 2010)

Alcohol intake and pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium (PanScan) - Dominique S. Michaud; Alina Vrieling; Li Jiao; Julie B. Mendelsohn; Emily Steplowski; Shannon M. Lynch; Jean Wactawski-Wende; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Charles S. Fuchs; Myron Gross; Kathy Helzlsouer; et al. (Cancer Causes & Control, 2010)

Analyzing complex traits with congenic strains - Haifeng Shao; David S. Sinasac; Lindsay C. Burrage; Craig A. Hodges; Pamela J. Supelak; Mark R. Palmert; Carol Moreno; Allen W. Cowley; Howard J. Jacob; Joseph H. Nadeau (Mammalian Genome, 2010)

Effect of Propranolol on Functional Connectivity in Autism Spectrum Disorder—A Pilot Study - Ananth Narayanan; Catherine A. White; Sanjida Saklayen; Mary J. Scaduto; Allen L. Carpenter; Amir Abduljalil; Petra Schmalbrock; David Q. Beversdorf (Brain Imaging and Behavior, 2010)

Biological consequences of invasion by reed canary grass (Phalaris arundinacea) - Greg Spyreas; Brian W. Wilm; Allen E. Plocher; David M. Ketzner; Jeffrey W. Matthews; James L. Ellis; Edward J. Heske (Biological Invasions, 2010)

Association between cervical dysplasia and human papillomavirus in HIV seropositive women from Johannesburg South Africa - Cynthia Firnhaber; Hoa Van Le; Audrey Pettifor; Doreen Schulze; Pam Michelow; Ian M. Sanne; David A. Lewis; Anna-Lise Williamson; Bruce Allan; Sophia Williams; Allen Rinas; Simon Levin; et al. (Cancer Causes & Control, 2010)

Sedimentation of acantharian cysts in the Iceland Basin: Strontium as a ballast for deep ocean particle flux, and implications for acantharian reproductive strategies - Patrick Martin; John T. Allen; Matthew J. Cooper; David G. Johns; Richard S. Lampitt; Richard Sanders; Damon A. H. Teagle (Limnology and Oceanography, 2010)
Acantharian cysts were discovered in sediment trap samples from spring 2007 at 2000 m in the Iceland Basin. Although these single‐celled organisms contribute to particulate organic matter flux in the upper mesopelagic, their contribution to bathypelagic particle flux has previously been found negligible. Four time‐series sediment traps were deployed and all collected acantharian cysts, which are reproductive structures. Across all traps, cysts contributed on average 3–22%, and 4–24% of particulate organic carbon and nitrogen (POC and PON) flux, respectively, during three separate collection intervals (the maximum contribution in any one trap was 48% for POC and 59% for PON). Strontium (Sr) flux during these 6 weeks reached 3 mg m −2 d −1 . The acantharian celestite (SrSO 4 ) skeleton clearly does not always dissolve in the mesopelagic as often thought, and their cysts can contribute significantly to particle flux at bathypelagic depths during specific flux events. Their large size (~ 1 mm) and mineral ballast result in a sinking rate of ~ 500 m d −1 ; hence, they reach the bathypelagic before dissolving. Our findings are consistent with a vertical profile of salinity‐normalized Sr concentration in the Iceland Basin, which shows a maximum at 1700 m. Profiles of salinity‐normalized Sr concentration in the subarctic Pacific reach maxima at ≤ 1500 m, suggesting that Acantharia might contribute to the bathypelagic particle flux there as well. We hypothesize that Acantharia at high latitudes use rapid, deep sedimentation of reproductive cysts during phytoplankton blooms so that juveniles can exploit the large quantity of organic matter that sinks rapidly to the deep sea following a bloom.

Top‐down control of microbial activity and biomass in an Arctic soil ecosystem - Bethany Allen; Dana Willner; Walter C. Oechel; David Lipson (Environmental Microbiology, 2010)
Summary Globally, soil microbes preside over vast carbon stores, and both microbial biomass and activity are known to be regulated by bottom‐up controls, that is, limitation by nutrients and energy. However, there is evidence that grazing by protozoans exerts top‐down controls on biomass. Here, we investigate top‐down control by phage on soil microbes using an experimental site near Barrow, Alaska (71°N, 157°W) during the 2007 growing season. Soil measurements were taken from sites that covered a range of microtopographical features within a drained and thawed lake basin including high‐ and low‐centred ice‐wedge polygons to estimate the availability of carbon and nitrogen for microbes. Using both field and laboratory experiments, we successfully increased both microbial biomass and respiration by decreasing phage populations. The addition of carbon and nutrients to soils had no significant effects on biomass or respiration, indicating a lack of bottom‐up controls. Additionally, we present the first use of tea extracts as a potent anti‐phage agent in soils. Our results suggest that top‐down controls, such as phage predation, are critical to regulation of microbial activities in Arctic soils.

Enzymatic properties of the ferredoxin-dependent nitrite reductase from Chlamydomonas reinhardtii. Evidence for hydroxylamine as a late intermediate in ammonia production - Masakazu Hirasawa; Jatindra N. Tripathy; Frederik Sommer; Ramasamy Somasundaram; Jung-Sung Chung; Matthew Nestander; Mahima Kruthiventi; Masoud Zabet-Moghaddam; Michael K. Johnson; Sabeeha S. Merchant; James P. Allen; David B. Knaff (Photosynthesis Research, 2010)

Global earthquake casualties due to secondary effects: a quantitative analysis for improving rapid loss analyses - Kristin D. Marano; David J. Wald; Trevor I. Allen (Natural Hazards, 2010)

Authors’ response to Kreiss et al. (2009) - David Allen Galbraith; David Weill (International Archives of Occupational and Environmental Health, 2010)

Yield and nutritional responses to waterlogging of soybean cultivars - Matthew Douglas Rhine; Gene Stevens; Grover Shannon; Allen Wrather; David Sleper (Irrigation Science, 2010)

Author’s response to Harber et al. (2008) - David Allen Galbraith; David Weill (International Archives of Occupational and Environmental Health, 2010)

Author’s response to Harber et al. (2008) - David Allen Galbraith; David Weill (International Archives of Occupational and Environmental Health, 2010)

Cerebral White Matter Integrity and Cognitive Aging: Contributions from Diffusion Tensor Imaging - David J. Madden; Ilana J. Bennett; Allen W. Song (Neuropsychology Review, 2009)

Estimates of the air quality benefits of using natural gas in industrial and transportation applications in Lima, Peru - Tammy Thompson; Yosuke Kimura; Cyril Durrenberger; Alba Webb; Ana Isabel Tejela Matias; Matt Fraser; David T. Allen (Clean Technologies and Environmental Policy, 2009)

From small hosts come big viruses: the complete genome of a second Ostreococcus tauri virus, OtV‐1 - Karen D. Weynberg; Michael J. Allen; Kevin Ashelford; David J. Scanlan; William H. Wilson (Environmental Microbiology, 2009)
Summary Ostreococcus tauri virus (OtV‐1) is a large double‐stranded DNA virus and a prospective member of the family Phycodnaviridae , genus Prasinovirus . OtV‐1 infects the unicellular marine green alga O. tauri , the smallest known free‐living eukaryote. Here we present the 191 761 base pair genome sequence of OtV‐1, which has 232 putative protein‐encoding and 4 tRNA‐encoding genes. Approximately 31% of the viral gene products exhibit a similarity to proteins of known functions in public databases. These include a variety of unexpected genes, for example, a PhoH‐like protein, a N ‐myristoyltransferase, a 3‐dehydroquinate synthase, a number of glycosyltransferases and methyltransferases, a prolyl 4‐hydroxylase, 6‐phosphofructokinase and a total of 8 capsid proteins. A total of 11 predicted genes share homology with genes found in the Ostreococcus host genome. In addition, an intein was identified in the DNA polymerase gene of OtV‐1. This is the first report of an intein in the genome of a virus that infects O. tauri. Fifteen core genes common to nuclear‐cytoplasmic large dsDNA virus (NCLDV) genomes were identified in the OtV‐1 genome. This new sequence data may help to redefine the classification of the core genes of these viruses and shed new light on their evolutionary history.

Measurement of spontaneous signal fluctuations in fMRI: adult age differences in intrinsic functional connectivity - Nan-kuei Chen; Ying-hui Chou; Allen W. Song; David J. Madden (Brain Structure and Function, 2009)

An Atlas of ShakeMaps and population exposure catalog for earthquake loss modeling - Trevor I. Allen; David J. Wald; Paul S. Earle; Kristin D. Marano; Alicia J. Hotovec; Kuowan Lin; Michael G. Hearne (Bulletin of Earthquake Engineering, 2009)

Interpollutant emission trading of ozone precursors in southeast Texas - Linlin Wang; David Allen; Elena McDonald-Buller (Clean Technologies and Environmental Policy, 2009)

Taking species abundance distributions beyond individuals - Hélène Morlon; Ethan P. White; Rampal S. Etienne; Jessica L. Green; Annette Ostling; David Alonso; Brian J. Enquist; Fangliang He; Allen Hurlbert; Anne E. Magurran; Brian A. Maurer; Brian J. McGill; et al. (Ecology Letters, 2009)
The species abundance distribution (SAD) is one of the few universal patterns in ecology. Research on this fundamental distribution has primarily focused on the study of numerical counts, irrespective of the traits of individuals. Here we show that considering a set of Generalized Species Abundance Distributions (GSADs) encompassing several abundance measures, such as numerical abundance, biomass and resource use, can provide novel insights into the structure of ecological communities and the forces that organize them. We use a taxonomically diverse combination of macroecological data sets to investigate the similarities and differences between GSADs. We then use probability theory to explore, under parsimonious assumptions, theoretical linkages among them. Our study suggests that examining different GSADs simultaneously in natural systems may help with assessing determinants of community structure. Broadening SADs to encompass multiple abundance measures opens novel perspectives in biodiversity research and warrants future empirical and theoretical developments.

Effects of sibutramine and rimonabant in rats trained to discriminate between 22- and 2-h food deprivation - David C. Jewett; Thomas W. Hahn; Travis R. Smith; Britta L. Fiksdal; Jason M. Wiebelhaus; Andrew R. Dunbar; Catherine R. Filtz; Noah L. Novinska; Allen S. Levine (Psychopharmacology, 2009)

Sustainable engineering education in the United States - Brad Allenby; Cynthia Folsom Murphy; David Allen; Cliff Davidson (Sustainability Science, 2009)

Modeling the effects of El Niño, density‐dependence, and disturbance on harbor seal ( Phoca vitulina ) counts in Drakes Estero, California: 1997–2007 - Benjamin H. Becker; David T. Press; Sarah G. Allen (Marine Mammal Science, 2009)
Harbor seal ( Phoca vitulina ) haul‐out site use may be affected by natural or anthropogenic factors. Here, we use an 11‐yr (1997–2007) study of a seal colony located near a mariculture operation in Drakes Estero, California, to test for natural (El Niño‐Southern Oscillation (ENSO), density‐dependence, long‐term trends) and anthropogenic (disturbance or displacement related to oyster production activities) factors that may influence the use of haul‐out subsites. Annual mariculture related seal disturbance rates increased significantly with increases in oyster harvest ( r s = 0.55). Using generalized linear models (GLMs) ranked by best fit and Akaike's Information Criteria, ENSO and oyster production (as a proxy for disturbance/displacement) best explained the patterns of seal use at all three subsites near the mariculture operations, with effects being stronger at the two subsites closest to operations. Conversely, density‐dependence and linear trend effects poorly explained the counts at these subsites. We conclude that a combination of ENSO and mariculture activities best explain the patterns of seal haul‐out use during the breeding/pupping season at the seal haul‐out sites closest to oyster activities.

Structure of Two Solanum bulbocastanum Polyubiquitin Genes and Expression of Their Promoters in Transgenic Potatoes - David R. Rockhold; Sophie Chang; Nathan Taylor; Paul V. Allen; Kent F. McCue; William R. Belknap (American Journal of Potato Research, 2008)

The effects of low‐shear stress on Adherent‐invasive Escherichia coli - Christopher A. Allen; David W. Niesel; Alfredo G. Torres (Environmental Microbiology, 2008)
Summary The impact of low‐shear stress (LSS) was evaluated on an Adherent‐invasive Escherichia coli clinical isolate (AIEC strain O83:H1) from a Crohn's disease patient. High‐aspect ratio vessels (HARVs) were used to model LSS conditions to characterize changes in environmental stress resistance and adhesion/invasive properties. Low‐shear stress‐grown cultures exhibited enhanced thermal and oxidative stress resistance as well as increased adherence to Caco‐2 cells, but no changes in invasion were observed. An AIEC rpoS mutant was constructed to examine the impact of this global stress regulator. The absence of RpoS under LSS conditions resulted in increased sensitivity to oxidative stress while adherence levels were elevated in comparison with the wild‐type strain. Tn phoA mutagenesis and rpoS complementation were carried out on the rpoS mutant to identify those factors involved in the LSS‐induced adherence phenotype. Mutagenesis results revealed that one insertion disrupted the tnaB gene (encoding tryptophan permease) and the rpoS tnaB double mutant exhibited decreased adherence under LSS. Complementation of the tnaB gene, or medium supplemented with exogenous indole, restored adhesion of the rpoS tnaB mutant under LSS conditions. Overall, our study demonstrated how mechanical stresses such as LSS altered AIEC phenotypic characteristics and identified novel functions for some RpoS‐regulated proteins.

ABOVEGROUND AND BELOWGROUND EFFECTS OF SINGLE‐TREE REMOVALS IN NEW ZEALAND RAIN FOREST - David A. Wardle; Susan K. Wiser; Robert B. Allen; James E. Doherty; Karen I. Bonner; Wendy M. Williamson (Ecology, 2008)
There has been considerable recent interest in how human‐induced species loss affects community and ecosystem properties. These effects are particularly apparent when a commercially valuable species is harvested from an ecosystem, such as occurs through single‐tree harvesting or selective logging of desired timber species in natural forests. In New Zealand mixed‐species rain forests, single‐tree harvesting of the emergent gymnosperm Dacrydium cupressinum, or rimu, has been widespread. This harvesting has been contentious in part because of possible ecological impacts of Dacrydium removal on the remainder of the forest, but many of these effects remain unexplored. We identified an area where an unintended 40‐year “removal experiment” had been set up that involved selective extraction of individual Dacrydium trees. We measured aboveground and belowground variables at set distances from both individual live trees and stumps of trees harvested 40 years ago. Live trees had effects both above and below ground by affecting diversity and cover of several components of the vegetation (usually negatively), promoting soil C sequestration, enhancing ratios of soil C:P and N:P, and affecting community structure of soil microflora. These effects extended to 8 m from the tree base and were likely caused by poor‐quality litter and humus produced by the trees. Measurements for the stumps revealed strong legacy effects of prior presence of trees on some properties (e.g., cover by understory herbs and ferns, soil C sequestration, soil C:P and N:P ratios), but not others (e.g., soil fungal biomass, soil N concentration). These results suggest that the legacy of prior presence of Dacrydium may remain for several decades or centuries, and certainly well over 40 years. They also demonstrate that, while large Dacrydium individuals (and their removal) may have important effects in their immediate proximity, within a forest, these effects should only be important in localized patches containing high densities of large trees. Finally, this study emphasizes that deliberate extraction of a particular tree species from a forest can exert influences both above and below ground if the removed species has a different functional role than that of the other plant species present.

Multimillion year thermal history of a porphyry copper deposit: application of U–Pb, 40Ar/39Ar and (U–Th)/He chronometers, Bajo de la Alumbrera copper–gold deposit, Argentina - Anthony C. Harris; W. James Dunlap; Peter W. Reiners; Charlotte M. Allen; David R. Cooke; Noel C. White; Ian H. Campbell; Suzanne D. Golding (Mineralium Deposita, 2008)

Structure and metal binding properties of ZnuA, a periplasmic zinc transporter from Escherichia coli - Liliya A. Yatsunyk; J. Allen Easton; Lydia R. Kim; Stacy A. Sugarbaker; Brian Bennett; Robert M. Breece; Ivan I. Vorontsov; David L. Tierney; Michael W. Crowder; Amy C. Rosenzweig (JBIC Journal of Biological Inorganic Chemistry, 2008)

The role of tryptophan in the ferredoxin-dependent nitrite reductase of spinach - Jatindra N. Tripathy; Masakazu Hirasawa; Sung-Kun Kim; Aaron T. Setterdahl; James P. Allen; David B. Knaff (Photosynthesis Research, 2007)

New alternative phosphorylation sites on the cyclin dependent kinase 1/cyclin a complex in p53-deficient human cells treated with etoposide: possible association with etoposide-induced apoptosis - Karen Higginbottom; Ulrike Jahnke; Adrian C. Newland; Finbarr E. Cotter; Paul David Allen (Apoptosis, 2007)

Species abundance distributions: moving beyond single prediction theories to integration within an ecological framework - Brian J. McGill; Rampal S. Etienne; John S. Gray; David Alonso; Marti J. Anderson; Habtamu Kassa Benecha; Maria Dornelas; Brian J. Enquist; Jessica L. Green; Fangliang He; Allen H. Hurlbert; Anne E. Magurran; et al. (Ecology Letters, 2007)
Species abundance distributions (SADs) follow one of ecology’s oldest and most universal laws – every community shows a hollow curve or hyperbolic shape on a histogram with many rare species and just a few common species. Here, we review theoretical, empirical and statistical developments in the study of SADs. Several key points emerge. (i) Literally dozens of models have been proposed to explain the hollow curve. Unfortunately, very few models are ever rejected, primarily because few theories make any predictions beyond the hollow‐curve SAD itself. (ii) Interesting work has been performed both empirically and theoretically, which goes beyond the hollow‐curve prediction to provide a rich variety of information about how SADs behave. These include the study of SADs along environmental gradients and theories that integrate SADs with other biodiversity patterns. Central to this body of work is an effort to move beyond treating the SAD in isolation and to integrate the SAD into its ecological context to enable making many predictions. (iii) Moving forward will entail understanding how sampling and scale affect SADs and developing statistical tools for describing and comparing SADs. We are optimistic that SADs can provide significant insights into basic and applied ecological science.

The rise of [Na+]i during ischemia and reperfusion in the rat heart—underlying mechanisms - Iwan A. Williams; Xiao-hui Xiao; Yue-kun Ju; David G. Allen (Pflügers Archiv - European Journal of Physiology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

In Vivo Performance of a Liposomal Vascular Contrast Agent for CT and MR-Based Image Guidance Applications - Jinzi Zheng; Jubo Liu; Mike Dunne; David A. Jaffray; Christine Allen (Pharmaceutical Research, 2007)

Museum samples provide novel insights into the taxonomy and genetic diversity of Irish red grouse - Joanna R. Freeland; Sarah Anderson; David Allen; Declan Looney (Conservation Genetics, 2007)

How useful is DNA extracted from the legs of archived insects for microsatellite-based population genetic analyses? - Phillip C. Watts; David J. Thompson; Katherine A. Allen; Stephen J. Kemp (Journal of Insect Conservation, 2007)

Groundwater flow patterns in the San Luis Valley, Colorado, USA revisited: an evaluation of solute and isotopic data - Alan L. Mayo; Allen Davey; David Christiansen (Hydrogeology Journal, 2007)

The Role of Cohort Studies in Drug Development: Clinical Evidence of Antiviral Activity of Serotonin Reuptake Inhibitors and HMG-CoA Reductase Inhibitors in the Central Nervous System - Scott L. Letendre; Jennifer Marquie-Beck; Ronald J. Ellis; Steven Paul Woods; Brookie Best; David B. Clifford; Ann C. Collier; Benjamin B. Gelman; Christina Marra; Justin C. McArthur; J. Allen McCutchan; Susan Morgello; et al. (Journal of Neuroimmune Pharmacology, 2007)

Teaching Sustainable Engineering - Braden R. Allenby; David T. Allen; Cliff I. Davidson (Journal of Industrial Ecology, 2007)

AICAR inhibits the Na+/H+ exchanger in rat hearts—possible contribution to cardioprotection - Terence R. Moopanar; Xiao-Hui Xiao; Lele Jiang; Zhi-Ping Chen; Bruce E. Kemp; David G. Allen (Pflügers Archiv - European Journal of Physiology, 2006)

Marble-hosted sulfide ores in the Angouran Zn-(Pb–Ag) deposit, NW Iran: interaction of sedimentary brines with a metamorphic core complex - H. Albert Gilg; Maria Boni; Giuseppina Balassone; Cameron R. Allen; David Banks; Farid Moore (Mineralium Deposita, 2006)

Sustainable engineering: a model for engineering education in the twenty-first century? - David T. Allen; Cynthia F. Murphy; Braden Allenby; Cliff Davidson (Clean Technologies and Environmental Policy, 2006)

Structural analysis of a designed inhibitor complexed with the hemagglutinin-neuraminidase of Newcastle disease virus - Charlotte Ryan; Viateslav Zaitsev; David J. Tindal; Jeffrey C. Dyason; Robin J. Thomson; Irina Alymova; Allen Portner; Mark von Itzstein; Garry Taylor (Glycoconjugate Journal, 2006)

Evidence and Implications of Recent Climate Change in Northern Alaska and Other Arctic Regions - Larry D. Hinzman; Neil D. Bettez; W. Robert Bolton; F. Stuart Chapin; Mark B. Dyurgerov; Chris L. Fastie; Brad Griffith; Robert D. Hollister; Allen Hope; Henry P. Huntington; Anne M. Jensen; Gensuo J. Jia; et al. (Climatic Change, 2005)

Introduction - James P. Allen; David B. Knaff (Photosynthesis Research, 2005)

Cyanide inhibits the Na+/Ca2+ exchanger in isolated cardiac pacemaker cells of the cane toad - Yue-kun Ju; David G. Allen (Pflügers Archiv - European Journal of Physiology, 2005)

Reversal or reduction of glutamate and GABA transport in CNS pathology and therapy - Nicola J. Allen; Ragnhildur Kradttir; David Attwell (Pflügers Archiv - European Journal of Physiology, 2004)

Cytokine gene polymorphisms in ischaemic heart disease: investigation using family-based tests of association - Paul G. McGlinchey; Mark S. Spence; Chris C. Patterson; Adrian R. Allen; Gillian Murphy; David A. Savage; A. Peter Maxwell; Pascal P. McKeown (Journal of Molecular Medicine, 2004)

Introduction - James P. Allen; David B. Knaff (Photosynthesis Research, 2004)

Analysis and glycosyl composition of the exopolysaccharide isolated from the floc‐forming wastewater bacterium Thauera sp. MZ1T - Michael S. Allen; Karen T. Welch; Benjamin S. Prebyl; David C. Baker; Arthur J. Meyers; Gary S. Sayler (Environmental Microbiology, 2004)
Summary Conditions were developed for the reproducible production, isolation and characterization of a novel microbial extracellular polysaccharide believed to be involved in transient viscous bulking at an industrial wastewater treatment plant. The exopolysaccharide was extracted from cell‐free culture supernatants of Thauera sp. strain MZ1T grown on a minimal medium with succinate. The purified polymer was found to be approximately 260 kDa in size by gel‐permeation chromatography. The GC–MS analysis of the alditol acetate and per‐ O ‐trimethylsilyl methyl glycoside derivatives revealed that the exopolysaccharide was composed of four monosaccharides including: rhamnose, galacturonic acid, N ‐acetylglucosamine and N ‐acetylfucosamine. Glucose, which also appeared at low levels, is most likely from a co‐eluting glucan. The FTIR and NMR spectroscopic analyses further revealed the presence of esterified component groups on the polymer. These results represent the first published description of a polysaccharide from a member of the genus Thauera , and lay the foundation for a deeper understanding of the factors potentially involved in zoogloeal cluster formation and viscous bulking.

The South Africa Stress and Health Study: Rationale and Design - David R. Williams; Allen Herman; Ronald C. Kessler; John Sonnega; Soraya Seedat; Dan J. Stein; Hashim Moomal; Colwick M. Wilson (Metabolic Brain Disease, 2004)

Genes controlling seed dormancy and pre-harvest sprouting in a rice-wheat-barley comparison - Chengdao Li; Peixiang Ni; Michael Francki; Adam Hunter; Yong Zhang; David Schibeci; Heng Li; Allen Tarr; Jun Wang; Mehmet Cakir; Jun Yu; Matthew Bellgard; et al. (Functional & Integrative Genomics, 2004)

Juxtamembrane localization of the protein phosphatase-1 inhibitor protein PHI-1 in smooth muscle cells - Nikolaos A. Tountas; James W. Mandell; Allen D. Everett; David L. Brautigan (Histochemistry and Cell Biology, 2004)

A small molecule antagonist of the α v β3 integrin suppresses MDA-MB-435 skeletal metastasis - John F. Harms; Danny R. Welch; Rajeev S. Samant; Lalita A. Shevde; Mary E. Miele; Geetha R. Babu; Steven F. Goldberg; Virginia R. Gilman; Donna M. Sosnowski; Dianalee A. Campo; Carol V. Gay; Lynn R. Budgeon; et al. (Clinical & Experimental Metastasis, 2004)

David M. Johns's "Necessity of New Alliances": an Immediate Opportunity - Brian Czech; Pat Magee; David Trauger; Eugene Allen; Helen Hands (Conservation Biology, 2004)

Black root rot: a pandemic in Australian cotton - David B. Nehl; Stephen J. Allen; Anowar H. Mondal; Peter A. Lonergan (Australasian Plant Pathology, 2004)

The distributional changes and role of microtubules in Nod factor-challenged Medicago sativa root hairs - Ravisha R. Weerasinghe; David A. Collings; Eva Johannes; Nina Strmgren Allen (Planta, 2003)

The cardioprotective effects of Na + /H + exchange inhibition and mitochondrial K ATP channel activation are additive in the isolated rat heart - Xiao-Hui Xiao; David G. Allen (Pflügers Archiv - European Journal of Physiology, 2003)

Mitochondrial DNA Clocks and the Phylogeny of Danaus Butterflies - Gugs Lushai; David A. S. Smith; Dave Goulson; John A. Allen; Norman Maclean (International Journal of Tropical Insect Science, 2003)

In Situ Blood–Brain Barrier Transport of Nanoparticles - Joanna M. Koziara; Paul R. Lockman; David D. Allen; Russell J. Mumper (Pharmaceutical Research, 2003)

Disturbances prevent stem size‐density distributions in natural forests from following scaling relationships - David A. Coomes; Richard P. Duncan; Robert B. Allen; James Truscott (Ecology Letters, 2003)
Enquist and Niklas propose that trees in natural forests have invariant size‐density distributions (SDDs) that scale as a −2 power of stem diameter, although early studies described such distributions using negative exponential functions. Using New Zealand and ‘global’ data sets, we demonstrate that neither type of function accurately describes the SDD over the entire diameter range. Instead, scaling functions provide the best fit to smaller stems, while negative exponential functions provide the best fit to larger stems. We argue that these patterns are consistent with competition shaping the small‐stem phase and exogenous disturbance shaping the large‐stem phase. Mortality rates, estimated from repeat measurements on 1546 New Zealand plots, fell precipitously with stem size until 18 cm but remained constant after that, consistent with our arguments. Even in the small‐stem phase, where SDDs were best described by scaling functions, the scaling exponents were not invariantly −2, but differed significantly from this value in both the ‘global’ and New Zealand data sets, and varied through time in the New Zealand data set.

US EPA/academia collaboration for a green engineering textbook for chemical engineering - David R. Shonnard; David T. Allen; Sharon Austin; Nhan Nguyen (Clean Technologies and Environmental Policy, 2003)

In Vivo and in Vitro Assessment of Baseline Blood-Brain Barrier Parameters in the Presence of Novel Nanoparticles - Paul R. Lockman; Joanna Koziara; Karen E. Roder; Jennifer Paulson; Thomas J. Abbruscato; Russell J. Mumper; David D. Allen (Pharmaceutical Research, 2003)

The Creation of an Historical Meteorological Database for Environmental Dose Assessment - Allen H. Weber; Robert L. Buckley; Matthew J. Parker; Richard P. Harvey; David M. Hamby (Environmental Monitoring and Assessment, 2003)

Factors Preventing the Recovery of New Zealand Forests Following Control of Invasive Deer - David A. Coomes; Robert B. Allen; David M. Forsyth; William G. Lee (Conservation Biology, 2003)
There is currently great interest in restoring ecosystems affected by invasive organisms. In New Zealand, deer were introduced during the nineteenth century, causing dramatic changes to the understory composition and structure of some forests. Deer prefer to browse on short tree species, mostly associated with early successional stands and moist‐fertile sites, but many tall tree species are browsed only when other food sources are scarce. The government has invested heavily in control programs aimed at reducing deer numbers and thereby restoring forests to something approaching their preinvasion composition and structure, but have met with only limited success. Based on a literature review, we give several examples of situations in which deer impacts may not be reversible, including the following: ( 1 ) palatable species remaining highly browsed even at low deer densities as a result of diet switching; ( 2 ) occupation of vacated niches by plant species not eaten by deer; ( 3 ) local extinction of seed sources; ( 4 ) fundamental alterations to successional pathways; ( 5 ) shifts in ecosystem processes; ( 6 ) other exotic animals becoming naturalized and weakening the effectiveness of single‐species control; and ( 7 ) exotic plants weakening the effectiveness of single‐species control. We consider the contributions that scientific research can make to effective forest restoration, including empirically based forest‐dynamics models that place regeneration in the context of other processes, such as disturbance, soil fertility, and multiple invasive organisms.

The role of endogenous angiotensin II in ischaemia, reperfusion and preconditioning of the isolated rat heart - Xiao-Hui Xiao; David G. Allen (Pflügers Archiv - European Journal of Physiology, 2003)

Geochemical Behavior of Arsenic in Kelly Lake, Ontario - Muhammad Sadiq; Allen Locke; Grame Spiers; David A. B. Pearson (Water, Air, & Soil Pollution, 2002)

High breast cancer incidence rates among California teachers: results from the California Teachers Study (United States) - Leslie Bernstein; Mark Allen; Hoda Anton-Culver; Dennis Deapen; Pamela L. Horn-Ross; David Peel; Richard Pinder; Peggy Reynolds; Jane Sullivan-Halley; Dee West; William Wright; Al Ziogas; et al. (Cancer Causes & Control, 2002)

Genetic and molecular control of folate-homocysteine metabolism in mutant mice - Sheila Ernest; Benedicte Christensen; Brian M. Gilfix; Orval A. Mamer; Angela Hosack; Mitchell Rodier; Clemencia Colmenares; James McGrath; Allen Bale; Rudi Balling; David Sankoff; David S. Rosenblatt; et al. (Mammalian Genome, 2002)

Intracellular ATP measured with luciferin/luciferase in isolated single mouse skeletal muscle fibres - David Allen; Jan Lännergren; Håkan Westerblad (Pflügers Archiv - European Journal of Physiology, 2002)

Ecosystem response to bivalve density reduction: management implications - Richard Dame; David Bushek; Dennis Allen; Alan Lewitus; Don Edwards; Eric Koepfler; Leah Gregory (Aquatic Ecology, 2002)

The importance of rapid, disturbance‐induced losses in carbon management and sequestration - David D. Breshears; Craig D. Allen (Global Ecology and Biogeography, 2002)
Management of terrestrial carbon fluxes is being proposed as a means of increasing the amount of carbon sequestered in the terrestrial biosphere. This approach is generally viewed only as an interim strategy for the coming decades while other longer‐term strategies are developed and implemented — the most important being the direct reduction of carbon emissions. We are concerned that the potential for rapid, disturbance‐induced losses may be much greater than is currently appreciated, especially by the decision‐making community. Here we wish to: (1) highlight the complex and threshold‐like nature of disturbances — such as fire and drought, as well as the erosion associated with each — that could lead to carbon losses; (2) note the global extent of ecosystems that are at risk of such disturbance‐induced carbon losses; and (3) call for increased consideration of and research on the mechanisms by which large, rapid disturbance‐induced losses of terrestrial carbon could occur . Our lack of ability as a scientific community to predict such ecosystem dynamics is precluding the effective consideration of these processes into strategies and policies related to carbon management and sequestration. Consequently, scientists need to do more to improve quantification of these potential losses and to integrate them into sound, sustainable policy options.

Comparing the Performance of Forest gap Models in North America - Harald K. M. Bugmann; Stan D. Wullschleger; David T. Price; Kiona Ogle; Donald F. Clark; Allen M. Solomon (Climatic Change, 2001)

Plankton dynamics: observed and modelled responses to physical conditions in Prince William Sound, Alaska - David L. Eslinger; R. Ted Cooney; C. Peter Mcroy; Alison Ward; Thomas C. Kline; E. Paul Simpson; Jia Wang; Jennifer R. Allen (Fisheries Oceanography, 2001)
Plankton populations in Prince William Sound, Alaska, exhibited pronounced seasonal, annual and longer‐period variability in composition and standing stock in response to physically influenced differences in nutrient availability, and possibly currents that modify local biomass by exchanges with water from the bordering Gulf of Alaska. During springs in which early, strong physical stratification developed, intense, short‐lived phytoplankton blooms occurred. These blooms had relatively short residence times in the water column. In contrast, during springs in which slower, weaker stratification developed, phytoplankton blooms were prolonged and took longer to peak. These slower blooms prolonged the period of phytoplankton production, prolonged interaction with the springtime grazing community and led to the incorporation of more organic matter into pelagic food webs. A coupled biological‐physical simulation of plankton production was used to examine the implications of seasonally varying air and mixed‐layer temperatures, surface winds and incident light on the timing, duration, annual production and standing stock of plankton. Our modelling results reproduced the observed characteristics of the springtime production cycle, and the magnitude of zooplankton stocks for the period 1992–97 but not for 1981–91. These results suggest that for most of the 1990s, bottom‐up influences on nutrient supplies controlled levels of primary consumers, whereas for the 11 years before that, other unknown factors dominated this process. We present the results of a comprehensive, multiyear study of relationships between plankton and physical limitations, and a retrospective analysis of earlier conditions to explore the possible causes for these differences.

Numerical simulations of the seasonal circulation patterns and thermohaline structures of Prince William Sound, Alaska - Jia Wang; Meibing Jin; E. Vincent Patrick; Jennifer R. Allen; David L. Eslinger; Christophee N. K. Mooers; R. Ted Cooney (Fisheries Oceanography, 2001)
A three‐dimensional, primitive‐equation ocean circulation model was applied to Prince William Sound, Alaska (3D‐PWS circulation model), under forcing of an ocean tide, freshwater runoff, surface heat flux, Alaska Coastal Current (ACC) throughflow (inflow/outflow), and daily (synoptic), spatially varying winds. The 3D structures and seasonal cycles of the circulation patterns, temperature, salinity (density), and mixed layer are examined. Freshwater runoff significantly contributes to the basin‐scale cyclonic circulation, which was not addressed in the previous simulations. Two typical circulation regimes, cyclonic and anticyclonic, characterize the complex flow patterns that depend on the intensities of the ACC thoughflow, freshwater discharge, and the synoptic wind. The spring (April–May) circulation pattern is characterized by a weak (maximum current 0.1 ms −1 ) anticyclonic flow in the central Sound, while the autumn (September–October) circulation is dominated by a basin‐scale, cyclonic gyre (maximum current 0.2 ms −1 ) due to the increase of the ACC throughflow and the maximum freshwater influence. During the summer, the circulation includes the cyclonic and anticyclonic gyres. During the winter, the circulation pattern is controlled by the basin‐scale cyclonic gyre and surface drift driven by the strong north‐easterly (south‐westward) wind forcing. The seasonal cycles of temperature (T) and salinity (S) vs. depth compare well with the observations. The simulated spring and autumn surface circulation patterns compare qualitatively well with the towed ADCP (acoustic Doppler current profilers) flow patterns and dynamic height patterns in the central Sound. An application of this model to zooplankton overwintering is discussed.

Photo-Degradation of Some Dyes using Ag-Loaded Titaniumdioxide - Münevver Sökmen; David W. Allen; Fatih Akkaş; Nuket Kartal; Filiz Acar (Water, Air, & Soil Pollution, 2001)

Hydrologic model for design and constructed wetlands - Jeffrey G. Arnold; Peter M. Allen; David S. Morgan (Wetlands, 2001)

Demonstration of prominent actin filaments in the root columella - David A. Collings; Gabor Zsuppan; Nina S. Allen; Elison B. Blancaflor (Planta, 2001)

The distribution of calcium in toad cardiac pacemaker cells during spontaneous firing - Yue-Kun Ju; David G. Allen (Pflügers Archiv - European Journal of Physiology, 2000)

Functional significance of Ca 2+ in long-lasting fatigue of skeletal muscle - Håkan Westerblad; Joseph D. Bruton; David G. Allen; Jan Lännergren (European Journal of Applied Physiology, 2000)

A Set of Core Principles and Tools? - David Allen (Journal of Industrial Ecology, 2000)

A revised sequence of the human β7 integrin gene ( ITGB7 ) promoter region obtained by inverse PCR - David A. van Heel; Maxine Allen; Derek P. Jewell; Alisoun H. Carey (Immunogenetics, 2000)

Lipoxygenase activity in seeds from New Zealand native plants - Catherine L. Allen; Jane E. Lancaster; David S. Robinson (New Zealand Journal of Botany, 1999)
Seeds from 48 New Zealand native plants, were tested for lipoxygenase enzymes and subsequent formation of products from linoleic and a‐linolenic acid. Lipoxygenases are of interest to the food and biotechnology industries as a means of producing natural flavour substances. Extracts of Gunnera hamiltonii possessed the highest lipoxygenase activity of 5.6. tmol min ‐1 g ‐1 . Analysis of the 13‐ and 9‐positional isomers of the oxidation products of linoleic acid showed that Melicystus lanceolatus × M. flexuosa, Pseudopanax arboreus, Carmichaelia kirkii, Dianella nigra , and Olearia paniculata produced higher proportions of the 13‐derivatives. Hoheria populnea, Solanum laciniatum , and Urtica australis produced predominately the 9‐isomers. Analysis of the 13‐ and 9‐positional isomers of the oxidation products of a‐linolenic acid showed that all species except Chionochloaflavescens were able to oxidise the trienoic acid to form 13‐positional isomers. Olearia ilicifolia produced only 13‐positional isomers. Only 11 of the species produced substantial amounts of the 9‐derivatives from a‐li‐nolenic acid. Chionochloaflavescens showed only the activity of a 9‐lipoxygenase.

Characterization of spontaneous metastasis in an aggressive breast carcinoma model using flow cytometry - Christina M. Schmidt; Steven L. Settle; Jeffery L. Keene; William F. Westlin; G. Allen Nickols; David W. Griggs (Clinical & Experimental Metastasis, 1999)

Sources of recently deposited sediments in playa wetlands - Hong-Ren Luo; Loren M. Smith; David A. Haukos; B. L. Allen (Wetlands, 1999)

Symposia lectures - F. Parak; A. Ostermann; G. U. Nienhaus; Nobuo Niimura; William A. Eaton; Stephen J. Hagen; Eric R. Henry; James Hofrichter; Gouri Jas; Lisa Lapidus; Victor Muñoz; Chih-chen Wang; et al. (Journal of Biosciences, 1999)

Genes encoding light-harvesting and reaction center proteins from Chromatium vinosum - Gary E. Corson; Kenji V. P. Nagashima; Katsumi Matsuura; Yumiko Sakuragi; Ruwanthi Wettasinghe; Hong Qin; Randy Allen; David B. Knaff (Photosynthesis Research, 1999)

Growth dynamics and cytoskeleton organization during stem maturation and gravity-induced stem bending in Zea mays L. - David A. Collings; Heike Winter; Sarah E. Wyatt; Nina S. Allen (Planta, 1998)

Material Reuse Modeling - Sara E. Keckler; David T. Allen (Journal of Industrial Ecology, 1998)
Summary The techniques of water distribution modeling, a well‐developed subject, have been applied to water management in an industrial park‐the Bayport chemical manufacturing complex in Houston, Texas in the United States. Linear and other mathematical programming approaches were used to evaluate water reuse opportunities for a variety of scenarios, including redesigning the industrial water use network, adding a facility to the network, limiting the total water available to the network, and varying the price of water rhe results of the modeling demonstrate that a number of economical water reuse opportunities may exist for this network of facilities. More generally, the types of mathematical models developed for water reuse may find application in reuse modeling for other materials.

Cotinine: effects with and without nicotine - D. Hatsukami; Paul R. Pentel; Joni Jensen; David Nelson; Sharon S. Allen; Anne Goldman; Donna Rafael (Psychopharmacology, 1998)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Measuring Corporate Environmental Performance: The ICI Environmental Burden System - Michael Wright; David Allen; Roland Clift; Hein Sas (Journal of Industrial Ecology, 1997)
Summary The Imperial Chemical Industries (ICI) group has developed a method, called the “environmental burden system” to rank the potential environmental impacts of its emissions and wastes. The method uses potency factors to characterize the potential environmental impacts of wastes and emissions in ten major impact categories. When compared to the more traditional approach of reporting the total mass of emissions and wastes, the environmental burden approach provides a more meaningful picture of the potential impact of emissions: it helps identi?. the most harmful wastes and emissions; it provides the public with a better understanding ofthe potential impact of company operations: and it helps communicate the effectiveness of waste and emission reduction programs

Compositional consistency of a heteropolysaccharide-7 produced by Beijerinckia indica - Jin W. Lee; Walter G. Yeomans; Alfred L. Allen; Richard A. Gross; David L. Kaplan (Biotechnology Letters, 1997)

Production of zoogloea gum by Zoogloea ramigerawith glucose analogs - Jin W. Lee; Walter G. Yeomans; Alfred L. Allen; Richard A. Gross; David L. Kaplan (Biotechnology Letters, 1997)

A polydisperse linear random coil model for the quaternary structure of pig colonic mucin - Kornelia Jumel; Fiona J. J. Fogg; David A. Hutton; J. P. Pearson; Adrian Allen; S. E. Harding (European Biophysics Journal, 1997)

Minimizing Chlorine Use: Assessing the Trade‐offs Between Cost and Chlorine Reduction in Chemical Manufacturing - Dennis Chang; David T. Allen (Journal of Industrial Ecology, 1997)
Summary A mathematical model ofthe material and energy flows in the chemical manufacturing industries was used to evaluate trade‐offs between cost and chlorine use in chemical manufaduring. The model was also used to assess the impact that new technologies could have on chlorine use. Although the cost data in the model were subject to considerable uncertainty, the results did provide general guidance in choosing chemical manufacturing technologies that reduce chlorine use in a cost‐effective way More significant, the modeling demonstrates that material flow data can play a critical role in assessing the environmental implications of industrial systems.

Abscisic acid inhibition of arachidonic acid-mediated rishitin synthesis in potato tuber discs - Dianne Shea; Robert D. Allen; Satish K. Bhatia; David A. Stelzig (American Journal of Potato Research, 1987)

Survival, growth, and accumulation of ingested lead in nestling American Kestrels (Falco sparverius) - David J. Hoffman; J. Christian Franson; Oliver H. Pattee; Christine M. Bunck; Allen Anderson (Archives of Environmental Contamination and Toxicology, 1985)

Sectional notes - Frank E. Garrett; David N. Wright; Cecil W. Frutchey; W. B. Ward; Allen Purdy; John C. Campbell; H. J. Evans; C. A. Henderson; W. C. Barnes; John Noonan; Edwin W. Cake; Claude R. Kemper; et al. (American Journal of Potato Research, 1948)